Thermoplastic elastomer composition

A thermoplastic elastomer composition using a block copolymer and ethylene-α-olefin copolymer addresses the issues of compression set and permanent growth in existing compositions, enhancing fluidity, flexibility, and mechanical properties of molded articles.

JP7621455B2Active Publication Date: 2025-01-24MITSUI CHEMICALS INC
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2023503768
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-03-05
Filing Date
2022-02-24
Publication Date
2025-01-24
Estimated Expiration
2042-02-24

AI Technical Summary

Technical Problem

Existing thermoplastic elastomer compositions, particularly those using paraffin mineral oil as a softening agent, lack sufficient resistance to compression set and permanent growth, especially when emphasizing fluidity and molding with SBC having a weight average molecular weight of about 100,000.

Method used

A thermoplastic elastomer composition is formulated using a block copolymer containing vinyl aromatic and conjugated diene compounds, combined with an ethylene-α-olefin copolymer and polyolefin resin, optimized for balance in fluidity, flexibility, and resistance to compression set and permanent elongation, achieved through specific molecular weight ranges and ratios.

Benefits of technology

The composition achieves an excellent balance of fluidity, flexibility, and resistance to compression set and permanent elongation, improving the mechanical properties and processability of molded articles.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007621455000001
    Figure 0007621455000001
  • Figure 0007621455000002
    Figure 0007621455000002
  • Figure 0007621455000003
    Figure 0007621455000003
Patent Text Reader

Abstract

One aspect of the present invention is a thermoplastic elastomer composition comprising: 100 parts by mass of (A) a block copolymer or a hydrogenated product thereof, the block copolymer containing a polymer block (X) mainly including a vinyl aromatic compound, and a polymer block (Y) mainly including a conjugated diene compound; 1 to 400 parts by mass of (B) an ethylene·α-olefin copolymer that satisfies the following requirements (b-1) to (b-3); and 0 to 200 parts by mass of (C) a polyolefin resin that satisfies the following requirement (c-1). (b-1) The kinematic viscosity at 100°C is 5 to 5,000 mm2 / s and the kinematic viscosity at 40°C is 50 to 100,000 mm2 / s. (b-2) The weight average molecular weight (Mw) determined by gel permeation chromatography (GPC) is 1,000 to 30,000. (b-3) The content ratio of an ethylene structural unit is 15 to 85 mol%. (c-1) MFR (230°C, 2.16 kg) is 0.1 to 500 g / 10 min.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] One aspect of the present invention relates to a thermoplastic elastomer composition containing an ethylene-α-olefin copolymer which is excellent in compression set, permanent elongation, etc. and satisfies specific requirements, or a molded article obtained therefrom. [Background technology]

[0002] Thermoplastic elastomers (TPEs) are materials that have the same melt moldability as thermoplastic resins such as polyethylene (PE) and polypropylene (PP), as well as flexibility and rubber elasticity similar to cross-linked rubber, and are used in a variety of applications such as automobiles, home appliances, food, medicine, and even daily necessities. There are various types of TPEs, including olefin-based elastomers (TPO), styrene-based elastomers (TPS), polyurethane-based elastomers (TPU), polyamide-based elastomers (TPA, TPAE), polyester-based elastomers (TPC, TPY), and vinyl chloride-based elastomers (TPVC).

[0003] Among these, TPS is a compound that uses styrene block copolymer (SBC) as the base resin. SBC is a general term for block copolymers in which the hard segment as the constrained phase is made of polystyrene. The soft segment is a conjugated diene polymer such as butadiene or isoprene, or its hydrogenated (hydrogenated) product. In SBC, the soft segment and hard segment have a microphase separation structure at room temperature, so the hard segment becomes a physical crosslinking point, and the performance (flexibility, rubber elasticity) of an elastomer is expressed without chemical crosslinking. At the same time, the physical crosslinking point made of polystyrene block can melt and break the crosslink by heating it to a temperature above its glass transition point, so unlike normal crosslinked rubber, it has thermoplasticity and can be melt molded. Among SBC, SBC with hydrogenated soft segments such as polybutadiene block and polyisoprene block (HSBC) does not have double bonds in the molecule and shows better heat resistance and weather resistance than non-hydrogenated SBC, so it is widely used as a TPS raw material.

[0004] In addition to SBC, TPS contains softeners such as mineral oil, thermoplastic resins such as polypropylene, and tackifiers such as petroleum resins, depending on the purpose. Of these, softeners are important compounding agents for improving the flexibility and rubber elasticity of TPS and its flowability (moldability) when melted, and paraffin-based mineral oils are commonly used.

[0005] Patent Document 1 discloses compositions in which a hydrogenated styrene-isoprene-styrene block copolymer, a hydrogenated styrene-(butadiene-isoprene)-styrene block copolymer, or a hydrogenated styrene-butadiene-styrene block copolymer is blended with mineral oil and polypropylene. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] Japanese Patent Application Publication No. 11-106565 Summary of the Invention [Problem to be solved by the invention]

[0007] However, in Patent Document 1, when paraffinic mineral oil is used as a softener for TPS, there is a problem that resistance to settling such as compression set and permanent elongation is insufficient. This problem is particularly prominent when the fluidity (moldability) of TPS is emphasized and an SBC with a weight-average molecular weight of about 100,000 is used. The present invention has been made in view of the above circumstances, and an object of the present invention is to provide a thermoplastic elastomer composition having excellent flowability, flexibility, and resistance to settling such as compression set and permanent elongation, and a molded article made of the composition. [Means for solving the problem]

[0008] Means for Solving the Problems The present inventors have conducted intensive studies aimed at solving the above problems and have found that by using a specific ethylene-α-olefin copolymer (B), it is possible to obtain a thermoplastic elastomer composition having an excellent balance of flowability, flexibility, and resistance to sagging, such as compression set and permanent elongation.

[0009] That is, one embodiment of the present invention relates to the following items [1] to

[11] . [1] 100 parts by mass of a block copolymer or a hydrogenated product thereof (A) containing a polymer block (X) mainly composed of a vinyl aromatic compound and a polymer block (Y) mainly composed of a conjugated diene compound; 1 to 400 parts by mass of an ethylene-α-olefin copolymer (B) satisfying the following requirements (b-1) to (b-3); 0 to 200 parts by mass of a polyolefin resin (C) satisfying the following requirement (c-1); 1. A thermoplastic elastomer composition comprising: (b-1) 100°C kinematic viscosity is 5 to 5,000mm 2 / s, and the kinetic viscosity at 40°C is 50 to 100,000 mm 2 / s. (b-2) The weight average molecular weight (Mw) determined by gel permeation chromatography (GPC) is 1,000 to 30,000. (b-3) The content of ethylene structural units is 15 to 85 mol%. (c-1) MFR (230°C, 2.16 kg) is 0.1 to 500 g / 10 min. [2] The block copolymer or hydrogenated product thereof (A) is a hydrogenated product of a block copolymer containing a polymer block (X) mainly made of a vinyl aromatic compound and a polymer block (Y) mainly made of a conjugated diene compound, The thermoplastic elastomer composition according to [1], wherein the content of the ethylene-α-olefin copolymer (B) is 30 to 300 parts by mass, and the content of the polyolefin resin (C) is 10 to 150 parts by mass, relative to 100 parts by mass of the hydrogenated block copolymer. [3] In the above requirement (b-1), the 100°C kinematic viscosity is 30 to 300 mm2 / s, and the kinetic viscosity at 40°C is 300 to 4,000 mm 2 / s, and In the above requirement (b-2), the weight average molecular weight (Mw) determined by gel permeation chromatography (GPC) is 2,000 to 7,000; and The thermoplastic elastomer composition according to [1] or [2], wherein, in the requirement (b-3), the content of ethylene structural units is 40 to 60 mol %. [4] The thermoplastic elastomer composition according to any one of [1] to [3], wherein the polymer block (X) is a polymer block mainly composed of styrene, the polymer block (Y) is a copolymer block mainly composed of butadiene and isoprene, and the block copolymer or its hydrogenated product (A) is a hydrogenated product of the block copolymer. [5] A sealing material comprising the thermoplastic elastomer composition according to any one of [1] to [4]. [6] An automobile interior material comprising the thermoplastic elastomer composition according to any one of [1] to [4]. [7] A vibration damping material comprising the thermoplastic elastomer composition according to any one of [1] to [4]. [8] 100 parts by mass of a block copolymer or a hydrogenated product thereof (A) containing a polymer block (X) mainly composed of a vinyl aromatic compound and a polymer block (Y) mainly composed of a conjugated diene compound; 1 to 400 parts by mass of an ethylene-α-olefin copolymer (B) produced by the following method (α) and satisfying the following requirements (b-1) to (b-3); 0 to 200 parts by mass of a polyolefin resin (C) satisfying the following requirement (c-1); A method for producing a thermoplastic elastomer composition, comprising the step of mixing (b-1) 100°C kinematic viscosity is 5 to 5,000mm 2 / s, and the kinetic viscosity at 40°C is 50 to 100,000 mm 2 / s. (b-2) The weight average molecular weight (Mw) determined by gel permeation chromatography (GPC) is 1,000 to 30,000. (b-3) The content of ethylene structural units is 15 to 85 mol%. (c-1) MFR (230°C, 2.16 kg) is 0.1 to 500 g / 10 min. Method (α): A bridged metallocene compound (P-1) represented by the following formula [1], and at least one compound (Q) selected from the group consisting of an organometallic compound (Q-1), an organoaluminum oxy compound (Q-2) and a compound (Q-3) which reacts with the bridged metallocene compound (P-1) to form an ion pair; 1. A process comprising the step of solution polymerizing ethylene and an α-olefin in the presence of a catalyst system comprising: [ka] [In formula [1], R 1 , R 2 , R 3 , R 4 , R 5 , R 8 , R 9 and R 12 each independently represents a hydrogen atom, a hydrocarbon group, or a silicon-containing hydrocarbon group, and adjacent groups may be linked to each other to form a ring structure; R 6 and R 11 are the same group and each is a hydrogen atom, a hydrocarbon group, or a silicon-containing hydrocarbon group, R 7 and R 10 are the same group and each is a hydrogen atom, a hydrocarbon group, or a silicon-containing hydrocarbon group, R 6 and R 7 may be bonded to a hydrocarbon having 2 to 3 carbon atoms to form a ring structure, R 10 and R 11 may be bonded to a hydrocarbon having 2 to 3 carbon atoms to form a ring structure, R 6 , R 7 , R 10 and R 11 is not a hydrogen atom at the same time; Y is a carbon atom or a silicon atom; R 13 and R 14 each independently represents a hydrogen atom, a hydrocarbon group, or a silicon-containing hydrocarbon group, and may be linked together to form a ring structure; M is Ti, Zr or Hf; Q is independently a halogen atom, a hydrocarbon group, an anionic ligand, or a neutral ligand capable of coordinating to a lone pair; j is an integer from 1 to 4. [9] In the formula [1], R 13 and R 14 wherein either or both of the above are aryl groups.

[10] In the formula [1], R 13 and R 14 are both aryl groups, and R 2 and R 3 wherein either one of the above is a saturated hydrocarbon group having 4 carbon atoms.

[11] The production method according to any one of [8] to

[10] , wherein the polymer block (X) is a polymer block mainly composed of styrene, the polymer block (Y) is a copolymer block mainly composed of butadiene and isoprene, and the block copolymer or its hydrogenated product (A) is a hydrogenated product of the block copolymer. Effect of the Invention

[0010] According to one aspect of the present invention, it is possible to provide a thermoplastic elastomer composition having an excellent balance of flowability, flexibility, and resistance to settling such as compression set and permanent elongation. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] The present invention will be specifically described below. In this specification, when a numerical range is indicated by "-", for example, "M to N", it means "M or more and N or less" unless otherwise specified.

[0012] In this specification, when an olefin constituting a certain polymer is represented by M, the expression "structural unit derived from M" is sometimes used, which means a "structural unit corresponding to M", that is, a structural unit having a pair of bonds formed by opening the π bond constituting the double bond of M.

[0013] In this specification, the term "(meth)acrylic" is used as a concept that encompasses acrylic, methacrylic, and both acrylic and methacrylic. A thermoplastic elastomer composition according to one embodiment of the present invention contains (A) a block copolymer or a hydrogenated product thereof shown below, (B) an ethylene-α-olefin copolymer shown below, and (C) a polyolefin resin shown below.

[0014] [A block copolymer or a hydrogenated product thereof (A) containing a polymer block (X) mainly made of a vinyl aromatic compound and a polymer block (Y) mainly made of a conjugated diene compound] The component (A) of the thermoplastic elastomer composition according to one embodiment of the present invention is a block copolymer or a hydrogenated product thereof, which contains a polymer block (X) mainly made of a vinyl aromatic compound and a polymer block (Y) mainly made of a conjugated diene compound. This block copolymer has a polymer block (X) mainly made of a vinyl aromatic compound and a polymer block (Y) mainly made of a conjugated diene compound, and is hereinafter also referred to as an "X / Y block copolymer."

[0015] Specific examples of the vinyl aromatic compound constituting the polymer block (X) include styrene, α-methylstyrene, 2-methylstyrene, 3-methylstyrene, 4-methylstyrene, 1,3-dimethylstyrene, 4-tert-butylstyrene, 1-vinylnaphthalene, 2-vinylnaphthalene, 4-propylstyrene, 4-isopropylstyrene, 4-cyclohexylstyrene, 4-dodecylstyrene, 2-ethyl-4-benzylstyrene, 4-(phenylbutyl)styrene, monochlorostyrene, dichlorostyrene, methoxystyrene, vinylanthracene, etc., and these vinyl aromatic compounds can be used alone or in combination. Among them, styrene is the most preferred.

[0016] The conjugated diene compound constituting the polymer block (Y) is preferably a conjugated diene having 4 to 20 carbon atoms, and specific examples thereof include 1,3-butadiene, isoprene (2-methyl-1,3-butadiene), 2,3-dimethyl-1,3-butadiene, 1,3-pentadiene, 1,3-hexadiene, etc., and one or more of these conjugated diene compounds can be used. Among these, butadiene and isoprene are most preferred.

[0017] Furthermore, the X / Y block copolymer containing the polymer block (X) and the polymer block (Y) preferably has a weight average molecular weight (Mw) in terms of polystyrene measured by GPC of 30,000 to 500,000, more preferably 50,000 to 400,000, further preferably 80,000 to 300,000, and particularly preferably 80,000 to 200,000. When the weight average molecular weight of the X / Y block copolymer is 30,000 or more, the settling resistance such as compression set and permanent elongation of the molded article obtained from the thermoplastic elastomer composition is improved, while when it is 500,000 or less, the moldability and processability are good.

[0018] The ratio of polymer block (X) to polymer block (Y) in an X / Y block copolymer depends on the number average molecular weight of the X / Y block copolymer, the number average molecular weights of polymer block (X) and polymer block (Y), etc., but in general, based on the mass of the X / Y block copolymer, the ratio of polymer block (X) is preferably 5 to 80 mass% and the ratio of polymer block (Y) is preferably 20 to 95 mass%, more preferably 10 to 75 mass% and 25 to 90 mass%, and further preferably 20 to 40 mass% and 60 to 80 mass%. In the X / Y block copolymer, when the proportion of the polymer block (X) is 5% by mass or more (i.e., when the proportion of the polymer block (Y) is 95% by mass or less), the thermoplastic elastomer composition containing the X / Y block copolymer and the molded article obtained therefrom have good resistance to settling, such as compression set and permanent elongation, while when the proportion of the polymer block (X) is 80% by mass or less (i.e., when the proportion of the polymer block (Y) is 20% by mass or more), the melt viscosity does not become too high and the moldability and processability are good.

[0019] The X / Y block copolymer may be either linear or branched with two or more branches, and the structure is not particularly limited as long as it has at least one polymer block (X) and at least one polymer block (Y) in the molecule. In view of the balance of mechanical properties, heat resistance, and processability, an XYX type triblock structure is particularly preferred.

[0020] Specific examples include styrene-butadiene-styrene block copolymers, styrene-isoprene-styrene block copolymers, styrene-butadiene / isoprene-styrene block copolymers, etc. For example, the styrene-butadiene-styrene block copolymer refers to a block copolymer in the form of polystyrene block-polybutadiene block-polystyrene block.

[0021] The method for producing the X / Y block copolymer is not particularly limited. For example, the X / Y block copolymer can be produced by sequentially polymerizing a vinyl aromatic compound such as styrene and a conjugated diene compound such as isoprene or butadiene in an inert solvent using a known method such as ionic polymerization such as anionic polymerization or cationic polymerization, radical polymerization, or coordination polymerization.

[0022] In the case of producing the copolymer by anionic polymerization, for example, an aliphatic hydrocarbon alkali metal compound, an aromatic hydrocarbon alkali metal compound, an organic amino alkali metal compound, or the like is used as a polymerization initiator to sequentially polymerize a vinyl aromatic compound and a conjugated diene compound in an inert organic solvent such as n-hexane or cyclohexane.

[0023] Among aliphatic hydrocarbon alkali metal compounds, aromatic hydrocarbon alkali metal compounds, and organic amino alkali metal compounds, aliphatic hydrocarbon lithium compounds or aromatic hydrocarbon lithium compounds are preferred as polymerization initiators.Specific examples include methyl lithium, ethyl lithium, n-propyl lithium, iso-propyl lithium, n-butyl lithium, sec-butyl lithium, tert-butyl lithium, n-hexyl lithium, the reaction product of diisopropenylbenzene and sec-butyl lithium, and further the reaction product of divinylbenzene, sec-butyl lithium, and a small amount of 1,3-butadiene, and the like, and particularly n-butyl lithium and sec-butyl lithium are preferred.

[0024] In addition, for the purpose of adjusting the vinyl bond rate (proportion of 1,2 or 1,3 bonds) of the conjugated diene compound, the molecular weight distribution of the copolymer, etc., an ether compound, a tertiary amine compound, etc. may be added. Examples of the ether compound include dimethyl ether, diethyl ether, diphenyl ether, tetrahydrofuran, 1,4-dioxane, etc., and examples of the tertiary amine compound include trimethylamine, triethylamine, tributylamine, N,N-dimethylaniline, N-methylpiperidine, N-methylpyrrolidine, N,N,N',N'-tetramethylethylenediamine, N-methylmorpholine, etc.

[0025] In the case of producing the copolymer by cationic polymerization, for example, a method can be mentioned in which a vinyl aromatic compound and a conjugated diene compound are sequentially polymerized in an inert organic solvent such as n-hexane or cyclohexane using a Lewis acid and an organic compound that generates a cationic polymerization active species by the Lewis acid as a polymerization initiator.

[0026] Examples of Lewis acids include titanium tetrachloride, tin tetrachloride, boron trichloride, aluminum chloride, etc., and examples of the organic compounds include organic compounds having functional groups such as alkoxy groups, acyloxy groups, or halogens, such as bis(2-methoxy-2-propyl)benzene, bis(2-acetoxy-2-propyl)benzene, bis(2-chloro-2-propyl)benzene, etc. Furthermore, together with the above Lewis acids and organic compounds, amides such as N,N-dimethylacetamide, and esters such as ethyl acetate may be used as a third component, if necessary.

[0027] Examples of the inert organic solvent used during polymerization include saturated hydrocarbon solvents such as pentane, hexane, heptane, octane, cyclopentane, methylcyclopentane, cyclohexane, and methylcyclohexane, and chlorine-based solvents such as methyl chloride and methylene chloride. One or more of these can be used.

[0028] The XYX type triblock copolymer, which is a particularly preferred embodiment of the component (A) used in one embodiment of the present invention, can be produced by, for example, (1) a method in which a compound that functions as a polymerization initiator for the anionic polymerization, cationic polymerization, or radical polymerization is used to polymerize a vinyl aromatic compound to form a polymer block (X), and then a conjugated diene compound is added to the reaction system and polymerized to form a polymer block (Y), and if necessary, a vinyl aromatic compound is further added and polymerized to form the polymer block (X); or (2) a method in which a compound that functions as a polymerization initiator for the anionic polymerization, cationic polymerization, or radical polymerization is used to polymerize a conjugated diene compound having two polymerization active functional groups to form a polymer block (Y), and then a vinyl aromatic compound is added to the reaction system and polymerized to form the polymer block (X).

[0029] As the component (A) according to one embodiment of the present invention, a hydrogenated product of the X / Y block copolymer can also be used. When a hydrogenated product is used, the number of aliphatic double bonds in the X / Y block copolymer is reduced by hydrogenation, thereby improving heat resistance and weather resistance, and improving compatibility with the ethylene-α-olefin copolymer (B) which is a softener, which is preferable.

[0030] The hydrogenated X / Y block copolymer used as component (A) according to one embodiment of the present invention is preferably one in which 90-100% of the aliphatic double bonds of the X / Y block copolymer are hydrogenated and 10% or less of the aromatic double bonds are hydrogenated, and more preferably one in which 99-100% of the aliphatic double bonds are hydrogenated and 5% or less of the aromatic double bonds are hydrogenated. In such a hydrogenated X / Y block copolymer, the polymer block (Y) in which the aliphatic double bonds are hydrogenated is substantially a block of polyolefin structure.

[0031] Examples of the hydrogenated X / Y block copolymer include styrene-(ethylene / butene)-styrene copolymer, styrene-(ethylene / propylene)-styrene copolymer, styrene-(ethylene / ethylene / propylene)-styrene copolymer, etc. In particular, the hydrogenated X / Y block copolymer is preferably a hydrogenated block copolymer containing a polymer block mainly composed of styrene and a copolymer block mainly composed of butadiene and isoprene.

[0032] A known method can be used for hydrogenating the X / Y block copolymer. For example, the X / Y block copolymer can be reacted in the presence of a hydrogenation catalyst and hydrogen under appropriate temperature and pressure conditions.

[0033] Examples of hydrogenation catalysts include (1) supported heterogeneous hydrogenation catalysts in which metals such as Ni, Pt, Pd, and Ru are supported on carbon, silica, alumina, and diatomaceous earth; (2) so-called Ziegler-type hydrogenation catalysts that use transition metal salts such as organic acid salts or acetylacetone salts of Ni, Co, Fe, and Cr and a reducing agent such as organoaluminum; and (3) homogeneous hydrogenation catalysts such as so-called organometallic complexes of organometallic compounds such as Ti, Ru, Rh, and Zr. The hydrogenation reaction is carried out at a temperature range of 0 to 200°C, more preferably 30 to 150°C. The hydrogen pressure used in the hydrogenation reaction is recommended to be 0.1 to 15 MPa, preferably 0.2 to 10 MPa, and more preferably 0.3 to 7 MPa. The hydrogenation reaction time is 3 minutes to 10 hours, preferably 10 minutes to 5 hours. The hydrogenation reaction can be carried out in any of a batch process, a continuous process, and a combination thereof.

[0034] As the X / Y block copolymer used as the component (A) according to one embodiment of the present invention, two or more kinds of X / Y block copolymers differing in properties such as molecular weight, styrene content, etc. may be used in combination.

[0035] The X / Y block copolymer used as component (A) according to one embodiment of the present invention is commercially available, and these commercially available products can be used. Examples of non-hydrogenated products include "D Series" manufactured by Kraton, "TR Series" manufactured by JSR, "Tufprene" and "Asaprene" manufactured by Asahi Kasei Corporation. Examples of hydrogenated products include "Septon" and "Hybra" manufactured by Kuraray, "Tuftec" manufactured by Asahi Kasei Corporation, "Dynaron" manufactured by JSR, and "G Series" manufactured by Kraton.

[0036] [Ethylene-α-olefin copolymer (B)] The ethylene / α-olefin copolymer (B) according to one aspect of the present invention is characterized by satisfying the following requirements (b-1) to (b-3).

[0037] Requirement (b-1) Kinematic viscosity at 100°C is 5 to 5,000 mm 2 / s, and the kinetic viscosity at 40°C is 50 to 100,000 mm 2 / s. The ethylene-α-olefin copolymer (B) according to one embodiment of the present invention has a kinematic viscosity at 100° C. of 5 to 5,000 mm 2 / s, preferably 10 to 3,000 mm 2 / s, more preferably 15 to 1,000 mm 2 / s, more preferably 15 to 500 mm 2 / s, and particularly preferably 30 to 300 mm 2 / s.

[0038] The ethylene-α-olefin copolymer (B) according to one embodiment of the present invention has a kinematic viscosity at 40° C. of 50 to 100,000 mm 2 / s, preferably 100 to 50,000 mm 2 / s, more preferably 130 to 15,000 mm 2 / s, and more preferably 130 to 8,000 mm 2 / s, and particularly preferably 300 to 4,000 mm 2 / s.

[0039] When the kinetic viscosity at 100°C and the kinetic viscosity at 40°C are within the above ranges, the balance between the handleability when kneading with the X / Y block copolymer (A) and the polyolefin resin (C) and the compression set and permanent elongation of the thermoplastic elastomer composition becomes extremely good.

[0040] Requirement (b-2) The weight average molecular weight (Mw) determined by gel permeation chromatography (GPC) is in the range of 1,000 to 30,000. The Mw of the ethylene / α-olefin copolymer (B) according to one embodiment of the present invention is 1,000 to 30,000, preferably 1,000 to 16,000, more preferably 1,300 to 10,000, still more preferably 1,500 to 8,000, and particularly preferably 2,000 to 7,000.

[0041] When the weight average molecular weight (Mw) determined by gel permeation chromatography (GPC) is within the above range, the balance between the handleability when kneading with the X / Y block copolymer (A) or the polyolefin resin (C) and the compression set and permanent elongation of the thermoplastic elastomer composition is extremely good.

[0042] Requirement (b-3) The content of ethylene structural units is 15 to 85 mol %. The ethylene structural unit content is 15 to 85 mol %, preferably 20 to 80 mol %, more preferably 30 to 70 mol %, and further preferably 40 to 60 mol %.

[0043] If the ethylene content is too high or too low, the crystallinity becomes high, which may deteriorate the handling property when kneading with the X / Y block copolymer (A) and the polyolefin resin (C), or may deteriorate the flexibility and low-temperature properties of the thermoplastic elastomer composition. If the ethylene content is too high or too low, the compatibility with the X / Y block copolymer (A), especially with the Y block of the X / Y block copolymer (A), may decrease, which may cause the ethylene-α-olefin copolymer (B) to bleed out from the thermoplastic elastomer composition, or may deteriorate the compression set and permanent elongation.

[0044] The ethylene content of the ethylene-α-olefin copolymer (B) is 13 The measurement can be performed by C-NMR method, and for example, peak identification and quantification can be performed according to the method described below and the method described in "Polymer Analysis Handbook" (published by Asakura Publishing, pp. 163-170).

[0045] Examples of the α-olefin constituting the ethylene-α-olefin copolymer (B) according to one embodiment of the present invention include α-olefins having 3 or more carbon atoms, and typical examples include α-olefins having 3 to 20 carbon atoms such as propylene, 1-butene, 1-pentene, 1-hexene, 1-heptene, 1-octene, 1-decene, 1-undecene, 1-dodecene, 1-tridecene, 1-tetradecene, 1-pentadecene, 1-hexadecene, 1-heptadecene, 1-octadecene, 1-nonadecene, and 1-eicosene. These α-olefins may be used alone or in combination of two or more.

[0046] Among these α-olefins, α-olefins having 3 to 10 carbon atoms are preferred, propylene and 1-butene are more preferred, and propylene is even more preferred, from the viewpoints that they can effectively reduce crystallinity, can provide a liquid copolymer, have excellent compatibility with the X / Y block copolymer (A), and can easily provide a composition and a molded article exhibiting the desired effects.

[0047] The polymerization can also be carried out by allowing at least one other monomer selected from a polar group-containing monomer, a vinyl aromatic compound, and a cyclic olefin to coexist in the reaction system. The other monomer can be used in an amount of, for example, 20 parts by mass or less, preferably 10 parts by mass or less, based on 100 parts by mass in total of ethylene and an α-olefin having 3 to 20 carbon atoms.

[0048] Examples of polar group-containing monomers include α,β-unsaturated carboxylic acids such as acrylic acid, methacrylic acid, fumaric acid, and maleic anhydride, and metal salts thereof such as sodium salts, α,β-unsaturated carboxylic acid esters such as methyl acrylate, ethyl acrylate, n-propyl acrylate, methyl methacrylate, and ethyl methacrylate, vinyl esters such as vinyl acetate and vinyl propionate, and unsaturated glycidyls such as glycidyl acrylate and glycidyl methacrylate.

[0049] Examples of vinyl aromatic compounds include styrene, o-methylstyrene, m-methylstyrene, p-methylstyrene, o,p-dimethylstyrene, methoxystyrene, vinylbenzoic acid, methyl vinylbenzoate, vinylbenzyl acetate, hydroxystyrene, p-chlorostyrene, divinylbenzene, α-methylstyrene, and allylbenzene.

[0050] Examples of the cyclic olefin include cyclic olefins having 3 to 30 carbon atoms, preferably 3 to 20 carbon atoms, such as cyclopentene, cycloheptene, norbornene, 5-methyl-2-norbornene, 5-ethylidene-2-norbornene, 5-vinyl-2-norbornene, and tetracyclododecene.

[0051] It is believed that the characteristics of the thermoplastic elastomer composition according to one embodiment of the present invention can be explained from the viewpoint of the chemical structures of the X / Y block copolymer (A) and the ethylene / α-olefin copolymer (B).

[0052] Generally used mineral oil-based softeners such as process oil soften both the X and Y blocks of the X / Y block copolymer (A), whereas the ethylene-α-olefin copolymer (B) can selectively soften only the Y block of the X / Y block copolymer (A). For this reason, the ethylene-α-olefin copolymer (B) can hold the X blocks, which are the physical crosslinking points of the X / Y block copolymer (A), more firmly than the mineral oil-based softeners, and as a result, it is considered that the ethylene-α-olefin copolymer (B) exhibits excellent mechanical properties such as compression set and permanent elongation.

[0053] The method for producing the ethylene-α-olefin copolymer (B) in one embodiment of the present invention is not particularly limited, but includes a method using a vanadium catalyst consisting of a vanadium compound and an organoaluminum compound, as described in JP-B-2-1163 and JP-B-2-7998. In addition, as a method for producing a copolymer with high polymerization activity, a method using a catalyst system consisting of a metallocene compound such as zirconocene and an organoaluminum oxy compound (aluminoxane), as described in JP-A-61-221207, JP-B-7-121969, and Japanese Patent No. 2796376, may be used, which is more preferable because it can reduce the chlorine content of the resulting copolymer and the 2,1-insertion of α-olefin. In the method using a vanadium catalyst, a larger amount of a chlorine compound is used as a cocatalyst than in the method using a metallocene catalyst, so there is a possibility that a trace amount of chlorine remains in the resulting ethylene-α-olefin copolymer (B).

[0054] In addition, the reduction in the 2,1-insertion of α-olefins makes it possible to further reduce the ethylene chains in the copolymer molecules, and since the intramolecular crystallinity of ethylene can be suppressed, an ethylene-α-olefin copolymer (B) having good compatibility with the X / Y block copolymer (A) can be obtained. The amount of 2,1-insertion of α-olefins can be reduced by the method described in JP-A-7-145212, 13It is determined by C-NMR measurement and analysis, and is preferably less than 1%, further preferably 0 to 0.5%, and even more preferably 0 to 0.1%. It is particularly preferable that no peak is observed in the range of 15.0 to 17.5 ppm.

[0055] In particular, by using the following method, an ethylene-α-olefin copolymer (B) having a good balance of performance in terms of molecular weight control, molecular weight distribution, amorphousness, etc. can be obtained.

[0056] The ethylene-α-olefin copolymer (B) according to one embodiment of the present invention can be produced by copolymerizing ethylene and an α-olefin having 3 to 20 carbon atoms in the presence of an olefin polymerization catalyst containing a bridged metallocene compound (P) represented by the following general formula [I], and at least one compound (Q) selected from the group consisting of an organometallic compound (Q-1), an organoaluminum oxy compound (Q-2), and a compound (Q-3) that reacts with the bridged metallocene compound (P) to form an ion pair.

[0057] [ka]

[0058] [Bridged metallocene compound (P)] The bridged metallocene compound (P) is represented by the above formula [I]. 1 ~R 14 , Q, n and j are explained below. (Y, M, R 1 ~R 14 , Q, n and j) Y is a Group 14 atom, examples of which include a carbon atom, a silicon atom, a germanium atom and a tin atom, and is preferably a carbon atom or a silicon atom, and more preferably a carbon atom.

[0059] M is a titanium atom, a zirconium atom or a hafnium atom, and is preferably a zirconium atom. R 1 ~R12 are atoms or substituents selected from the group consisting of hydrogen atoms, hydrocarbon groups having 1 to 20 carbon atoms, silicon-containing groups, nitrogen-containing groups, oxygen-containing groups, halogen atoms and halogen-containing groups, and may be the same or different. 1 From R 12 Adjacent substituents up to may be bonded to each other to form a ring, or may not be bonded to each other.

[0060] Here, examples of the hydrocarbon group having 1 to 20 carbon atoms include an alkyl group having 1 to 20 carbon atoms, a cyclic saturated hydrocarbon group having 3 to 20 carbon atoms, a linear unsaturated hydrocarbon group having 2 to 20 carbon atoms, a cyclic unsaturated hydrocarbon group having 3 to 20 carbon atoms, an alkylene group having 1 to 20 carbon atoms, and an arylene group having 6 to 20 carbon atoms.

[0061] Examples of the alkyl group having 1 to 20 carbon atoms include linear saturated hydrocarbon groups such as methyl, ethyl, n-propyl, allyl, n-butyl, n-pentyl, n-hexyl, n-heptyl, n-octyl, n-nonyl, and n-butyl. Decile and branched saturated hydrocarbon groups such as an isopropyl group, an isobutyl group, a s-butyl group, a t-butyl group, a t-amyl group, a neopentyl group, a 3-methylpentyl group, a 1,1-diethylpropyl group, a 1,1-dimethylbutyl group, a 1-methyl-1-propylbutyl group, a 1,1-propylbutyl group, a 1,1-dimethyl-2-methylpropyl group, a 1-methyl-1-isopropyl-2-methylpropyl group, and a cyclopropylmethyl group. The alkyl group preferably has 1 to 6 carbon atoms.

[0062] Examples of cyclic saturated hydrocarbon groups having 3 to 20 carbon atoms include cyclic saturated hydrocarbon groups such as cyclopropyl, cyclobutyl, cyclopentyl, cyclohexyl, cycloheptyl, cyclooctyl, norbornenyl, 1-adamantyl, and 2-adamantyl, and groups in which hydrogen atoms of cyclic saturated hydrocarbon groups are replaced with hydrocarbon groups having 1 to 17 carbon atoms such as 3-methylcyclopentyl, 3-methylcyclohexyl, 4-methylcyclohexyl, 4-cyclohexylcyclohexyl, and 4-phenylcyclohexyl. The number of carbon atoms in the cyclic saturated hydrocarbon group is preferably 5 to 11.

[0063] Examples of the linear unsaturated hydrocarbon group having 2 to 20 carbon atoms include alkenyl groups such as ethenyl group (vinyl group), 1-propenyl group, 2-propenyl group (allyl group), 1-methylethenyl group (isopropenyl group), etc., and alkynyl groups such as ethynyl group, 1-propynyl group, 2-propynyl group (propargyl group), etc. The number of carbon atoms in the linear unsaturated hydrocarbon group is preferably 2 to 4.

[0064] Examples of the cyclic unsaturated hydrocarbon group having 3 to 20 carbon atoms include cyclic unsaturated hydrocarbon groups such as cyclopentadienyl, norbornyl, phenyl, naphthyl, indenyl, azulenyl, phenanthryl, and anthracenyl, groups in which hydrogen atoms of cyclic unsaturated hydrocarbon groups are replaced with hydrocarbon groups having 1 to 15 carbon atoms such as 3-methylphenyl (m-tolyl), 4-methylphenyl (p-tolyl), 4-ethylphenyl, 4-t-butylphenyl, 4-cyclohexylphenyl, biphenylyl, 3,4-dimethylphenyl, 3,5-dimethylphenyl, and 2,4,6-trimethylphenyl (mesityl), groups in which hydrogen atoms of linear hydrocarbon groups or branched saturated hydrocarbon groups are replaced with cyclic saturated hydrocarbon groups or cyclic unsaturated hydrocarbon groups having 3 to 19 carbon atoms such as benzyl and cumyl. The number of carbon atoms of the cyclic unsaturated hydrocarbon group is preferably 6 to 10.

[0065] Examples of the alkylene group having 1 to 20 carbon atoms include a methylene group, an ethylene group, a dimethylmethylene group (an isopropylidene group), an ethylmethylene group, a methylethylene group, an n-propylene group, etc. The number of carbon atoms in the alkylene group is preferably 1 to 6.

[0066] Examples of the arylene group having 6 to 20 carbon atoms include an o-phenylene group, an m-phenylene group, a p-phenylene group, a 4,4'-biphenylylene group, etc. The number of carbon atoms in the arylene group is preferably 6 to 12.

[0067] Examples of the silicon-containing group include alkylsilyl groups such as trimethylsilyl group, triethylsilyl group, t-butyldimethylsilyl group, and triisopropylsilyl group, which are groups in which carbon atoms in a hydrocarbon group having 1 to 20 carbon atoms are replaced with silicon atoms, arylsilyl groups such as dimethylphenylsilyl group, methyldiphenylsilyl group, and t-butyldiphenylsilyl group, pentamethyldisilanyl group, and trimethylsilylmethyl group, etc. The number of carbon atoms in the alkylsilyl group is preferably 1 to 10, and the number of carbon atoms in the arylsilyl group is preferably 6 to 18.

[0068] Examples of the nitrogen-containing group include an amino group, a group in which the =CH- structural unit in the above-mentioned hydrocarbon group having 1 to 20 carbon atoms or silicon-containing group is replaced with a nitrogen atom, a group in which the -CH2- structural unit is replaced with a nitrogen atom to which a hydrocarbon group having 1 to 20 carbon atoms is bonded, or a group in which the -CH3 structural unit is replaced with a nitrogen atom to which a hydrocarbon group having 1 to 20 carbon atoms is bonded or a nitrile group, such as a dimethylamino group, a diethylamino group, an N-morpholinyl group, a dimethylaminomethyl group, a cyano group, a pyrrolidinyl group, a piperidinyl group, a pyridinyl group, an N-morpholinyl group, and a nitro group. As the nitrogen-containing group, a dimethylamino group and an N-morpholinyl group are preferred.

[0069] Examples of the oxygen-containing group include a hydroxyl group, a group in which the -CH2- structural unit in the above-mentioned hydrocarbon group having 1 to 20 carbon atoms, silicon-containing group or nitrogen-containing group is replaced with an oxygen atom or a carbonyl group, or a group in which the -CH3 structural unit is replaced with an oxygen atom bonded to a hydrocarbon group having 1 to 20 carbon atoms, such as a methoxy group, ethoxy group, t-butoxy group, phenoxy group, trimethylsiloxy group, methoxyethoxy group, hydroxymethyl group, methoxymethyl group, ethoxymethyl group, t-butoxymethyl group, 1-hydroxyethyl group, 1-methyl ... Examples of the oxygen-containing group include 1-methoxyethyl group, 1-ethoxyethyl group, 2-hydroxyethyl group, 2-methoxyethyl group, 2-ethoxyethyl group, n-2-oxabutylene group, n-2-oxapentylene group, n-3-oxapentylene group, aldehyde group, acetyl group, propionyl group, benzoyl group, trimethylsilylcarbonyl group, carbamoyl group, methylaminocarbonyl group, carboxy group, methoxycarbonyl group, carboxymethyl group, ethoxycarboxymethyl group, carbamoylmethyl group, furanyl group, and pyranyl group. As the oxygen-containing group, a methoxy group is preferable.

[0070] Examples of halogen atoms include Group 17 elements such as fluorine, chlorine, bromine, and iodine. Examples of the halogen-containing group include a trifluoromethyl group, a tribromomethyl group, a pentafluoroethyl group, a pentafluorophenyl group, and the like, which are groups in which a hydrogen atom in the above-mentioned hydrocarbon group having 1 to 20 carbon atoms, silicon-containing group, nitrogen-containing group, or oxygen-containing group is substituted with a halogen atom.

[0071] Q may be the same or different and selected in combination from a halogen atom, a hydrocarbon group having 1 to 20 carbon atoms, an anionic ligand, and a neutral ligand capable of coordinating with a lone electron pair. Details of the halogen atom and the hydrocarbon group having 1 to 20 carbon atoms are as described above. When Q is a halogen atom, it is preferably a chlorine atom. When Q is a hydrocarbon group having 1 to 20 carbon atoms, the hydrocarbon group preferably has 1 to 7 carbon atoms.

[0072] Examples of the anionic ligand include alkoxy groups such as methoxy, t-butoxy, and phenoxy groups; carboxylate groups such as acetate and benzoate; and sulfonate groups such as mesylate and tosylate.

[0073] Examples of neutral ligands capable of coordinating with lone electron pairs include organic phosphorus compounds such as trimethylphosphine, triethylphosphine, triphenylphosphine, and diphenylmethylphosphine, and ether compounds such as tetrahydrofuran, diethyl ether, dioxane, and 1,2-dimethoxyethane.

[0074] j is an integer of 1 to 4, and is preferably 2. n is an integer of 1 to 4, preferably 1 or 2, and more preferably 1. R 13 and R 14 are atoms or substituents selected from the group consisting of hydrogen atoms, hydrocarbon groups having 1 to 20 carbon atoms, aryl groups, substituted aryl groups, silicon-containing groups, nitrogen-containing groups, oxygen-containing groups, halogen atoms and halogen-containing groups, and may be the same or different. 13 and R 14 may be bonded to each other to form a ring, or may not be bonded to each other.

[0075] Details of the hydrocarbon group having 1 to 20 carbon atoms, the silicon-containing group, the nitrogen-containing group, the oxygen-containing group, the halogen atom and the halogen-containing group are as described above. Examples of the aryl group include, but are not limited to, the above-mentioned examples of the cyclic unsaturated hydrocarbon group having 3 to 20 carbon atoms, and are exemplified by substituents derived from aromatic compounds, such as phenyl, 1-naphthyl, 2-naphthyl, anthracenyl, phenanthrenyl, tetracenyl, chrysenyl, pyrenyl, indenyl, azulenyl, pyrrolyl, pyridyl, furanyl, and thiophenyl groups. The aryl group is preferably a phenyl group or a 2-naphthyl group.

[0076] Examples of the aromatic compounds include aromatic hydrocarbons and heterocyclic aromatic compounds such as benzene, naphthalene, anthracene, phenanthrene, tetracene, chrysene, pyrene, indene, azulene, pyrrole, pyridine, furan, and thiophene.

[0077] The substituted aryl group partially overlaps with the above-mentioned examples of the cyclic unsaturated hydrocarbon group having 3 to 20 carbon atoms, but examples thereof include groups in which one or more hydrogen atoms of the aryl group are substituted with at least one substituent selected from the group consisting of a hydrocarbon group having 1 to 20 carbon atoms, an aryl group, a silicon-containing group, a nitrogen-containing group, an oxygen-containing group, a halogen atom, and a halogen-containing group. Specific examples thereof include a 3-methylphenyl group (m-tolyl group), a 4-methylphenyl group (p-tolyl group), a 3-ethylphenyl group, a 4-ethylphenyl group, a 3,4-dimethylphenyl group, a 3,5-dimethylphenyl group, a biphenylyl group, a 4-(trimethylsilyl)phenyl group, a 4- Examples of the alkyl group include an aminophenyl group, a 4-(dimethylamino)phenyl group, a 4-(diethylamino)phenyl group, a 4-morpholinylphenyl group, a 4-methoxyphenyl group, a 4-ethoxyphenyl group, a 4-phenoxyphenyl group, a 3,4-dimethoxyphenyl group, a 3,5-dimethoxyphenyl group, a 3-methyl-4-methoxyphenyl group, a 3,5-dimethyl-4-methoxyphenyl group, a 3-(trifluoromethyl)phenyl group, a 4-(trifluoromethyl)phenyl group, a 3-chlorophenyl group, a 4-chlorophenyl group, a 3-fluorophenyl group, a 4-fluorophenyl group, a 5-methylnaphthyl group, and a 2-(6-methyl)pyridyl group.

[0078] Among them, R 13 and R 14 Preferably, one or both of R 13 and R 14 More preferred are bridged metallocene compounds (P) in which both are independently an aryl group, and R 13 and R 14 are both independently an aryl group, and R 2 and R 3More preferably, either one of the above is a saturated hydrocarbon group having 4 carbon atoms.

[0079] Such a bridged metallocene compound (P) has high polymerization activity for copolymerization of ethylene and α-olefin, and the use of this bridged metallocene compound (P) selectively terminates polymerization by introduction of hydrogen into the molecular end, resulting in fewer unsaturated bonds in the resulting ethylene-α-olefin copolymer (B). Therefore, an ethylene-α-olefin copolymer (B) having a high degree of saturation and excellent heat resistance can be obtained by simply carrying out a simpler hydrogen addition operation or even without carrying out a hydrogen addition operation, and is also excellent in terms of cost. In addition, the ethylene-α-olefin copolymer (B) obtained from the compound (P) has a controlled molecular weight distribution due to its high random copolymerization. Therefore, the thermoplastic elastomer composition according to one embodiment of the present invention containing the ethylene-α-olefin copolymer (B) is considered to have a well-balanced excellent level of moldability and sag resistance.

[0080] In the bridged metallocene compound (P) represented by the above formula [I], n is preferably 1. Such a bridged metallocene compound (hereinafter also referred to as "bridged metallocene compound (P-1)") is represented by the following general formula [1].

[0081] [ka] In formula [1], Y, M, and R 1 ~R 14 The definitions of Q and j are as described above.

[0082] The bridged metallocene compound (P-1) has a simplified production process and reduced production costs compared to the compound in the above formula [I] where n is an integer of 2 to 4. Thus, the use of this bridged metallocene compound (P-1) has the advantage of reducing the production costs of the ethylene-α-olefin copolymer (B).

[0083] In the bridged metallocene compound (P) represented by the above general formula [I] and the bridged metallocene compound (P-1) represented by the above general formula [1], M is more preferably a zirconium atom. When ethylene and one or more monomers selected from α-olefins having 3 to 20 carbon atoms are copolymerized in the presence of an olefin polymerization catalyst containing the above bridged metallocene compound in which M is a zirconium atom, the polymerization activity is higher than when M is a titanium atom or a hafnium atom, and the production cost of the ethylene-α-olefin copolymer (B) can be advantageously reduced.

[0084] Examples of such bridged metallocene compounds (P) include [Dimethylmethylene(η 5 -cyclopentadienyl)(η 5 -fluorenyl)]zirconium dichloride, [dimethylmethylene(η 5 -cyclopentadienyl)(η 5 -2,7-di-t-butylfluorenyl)]zirconium dichloride, [dimethylmethylene(η 5 -cyclopentadienyl)(η 5 -3,6-di-t-butylfluorenyl)]zirconium dichloride, [dimethylmethylene(η 5 -cyclopentadienyl)(η 5 -Octamethyloctahydrodibenzofluorenyl)]zirconium dichloride, [Dimethylmethylene(η 5 -cyclopentadienyl)(η 5 -tetramethyloctahydrodibenzofluorenyl)]zirconium dichloride, [Cyclohexylidene(η 5 -cyclopentadienyl)(η 5 -fluorenyl)]zirconium dichloride, [cyclohexylidene(η 5 -cyclopentadienyl)(η 5 -2,7-di-t-butylfluorenyl)]zirconium dichloride, [cyclohexylidene(η 5 -cyclopentadienyl)(η 5-3,6-di-t-butylfluorenyl)]zirconium dichloride, [cyclohexylidene(η 5 -cyclopentadienyl)(η 5 -Octamethyloctahydrodibenzofluorenyl)]zirconium dichloride, [cyclohexylidene(η 5 -cyclopentadienyl)(η 5 -tetramethyloctahydrodibenzofluorenyl)]zirconium dichloride, [Diphenylmethylene(η 5 -cyclopentadienyl)(η 5 -fluorenyl)]zirconium dichloride, [diphenylmethylene(η 5 -cyclopentadienyl)(η 5 -2,7-di-t-butylfluorenyl)]zirconium dichloride, [diphenylmethylene(η 5 -2-methyl-4-t-butylcyclopentadienyl)(η 5 -2,7-di-t-butylfluorenyl)]zirconium dichloride, [diphenylmethylene(η 5 -cyclopentadienyl)(η 5 -3,6-di-t-butylfluorenyl)]zirconium dichloride, [diphenylmethylene(η 5 -cyclopentadienyl)(η 5 -Octamethyloctahydrodibenzofluorenyl)]zirconium dichloride, [diphenylmethylene{η 5 -(2-methyl-4-i-propylcyclopentadienyl)}(η 5 -Octamethyloctahydrodibenzofluorenyl)]zirconium dichloride, [diphenylmethylene(η 5 -cyclopentadienyl)(η 5 -tetramethyloctahydrodibenzofluorenyl)]zirconium dichloride, [Methylphenylmethylene(η 5 -cyclopentadienyl)(η 5 -fluorenyl)]zirconium dichloride, [methylphenylmethylene(η 5 -cyclopentadienyl)(η 5-2,7-di-t-butylfluorenyl)]zirconium dichloride, [methylphenylmethylene(η 5 -cyclopentadienyl)(η 5 -3,6-di-t-butylfluorenyl)]zirconium dichloride, [methylphenylmethylene(η 5 -cyclopentadienyl)(η 5 -Octamethyloctahydrodibenzofluorenyl)]zirconium dichloride, [methylphenylmethylene(η 5 -cyclopentadienyl)(η 5 -tetramethyloctahydrodibenzofluorenyl)]zirconium dichloride, [Methyl(3-methylphenyl)methylene(η 5 -cyclopentadienyl)(η 5 -fluorenyl)]zirconium dichloride, [methyl(3-methylphenyl)methylene(η 5 -cyclopentadienyl)(η 5 -2,7-di-t-butylfluorenyl)]zirconium dichloride, [methyl(3-methylphenyl)methylene(η 5 -cyclopentadienyl)(η 5 -3,6-di-t-butylfluorenyl)]zirconium dichloride, [methyl(3-methylphenyl)methylene(η 5 -cyclopentadienyl)(η 5 -Octamethyloctahydrodibenzofluorenyl)]zirconium dichloride, [methyl(3-methylphenyl)methylene(η 5 -cyclopentadienyl)(η 5 -tetramethyloctahydrodibenzofluorenyl)]zirconium dichloride, [Methyl(4-methylphenyl)methylene(η 5 -cyclopentadienyl)(η 5 -fluorenyl)]zirconium dichloride, [methyl(4-methylphenyl)methylene(η 5 -cyclopentadienyl)(η 5 -2,7-di-t-butylfluorenyl)]zirconium dichloride, [methyl(4-methylphenyl)methylene(η 5-cyclopentadienyl)(η 5 -3,6-di-t-butylfluorenyl)]zirconium dichloride, [methyl(4-methylphenyl)methylene(η 5 -cyclopentadienyl)(η 5 -Octamethyloctahydrodibenzofluorenyl)]zirconium dichloride, [methyl(4-methylphenyl)methylene(η 5 -cyclopentadienyl)(η 5 -tetramethyloctahydrodibenzofluorenyl)]zirconium dichloride, [Diphenylsilylene(η 5 -cyclopentadienyl)(η 5 -fluorenyl)]zirconium dichloride, [diphenylsilylene(η 5 -cyclopentadienyl)(η 5 -2,7-di-t-butylfluorenyl)]zirconium dichloride, [diphenylsilylene(η 5 -cyclopentadienyl)(η 5 -3,6-di-t-butylfluorenyl)]zirconium dichloride, [diphenylsilylene(η 5 -cyclopentadienyl)(η 5 -Octamethyloctahydrodibenzofluorenyl)]zirconium dichloride, [diphenylsilylene(η 5 -cyclopentadienyl)(η 5 -tetramethyloctahydrodibenzofluorenyl)]zirconium dichloride, [Bis(3-methylphenyl)silylene(η 5 -cyclopentadienyl)(η 5 -fluorenyl)]zirconium dichloride, [bis(3-methylphenyl)silylene(η 5 -cyclopentadienyl)(η 5 -2,7-di-t-butylfluorenyl)]zirconium dichloride, [bis(3-methylphenyl)silylene(η 5 -cyclopentadienyl)(η 5 -3,6-di-t-butylfluorenyl)]zirconium dichloride, [bis(3-methylphenyl)silylene(η 5-cyclopentadienyl)(η 5 -octamethyloctahydrodibenzofluorenyl)]zirconium dichloride, [bis(3-methylphenyl)silylene(η 5 -cyclopentadienyl)(η 5 -tetramethyloctahydrodibenzofluorenyl)]zirconium dichloride, [Dicyclohexylsilylene(η 5 -cyclopentadienyl)(η 5 -fluorenyl)]zirconium dichloride, [dicyclohexylsilylene(η 5 -cyclopentadienyl)(η 5 -2,7-di-t-butylfluorenyl)]zirconium dichloride, [dicyclohexylsilylene(η 5 -cyclopentadienyl)(η 5 -3,6-di-t-butylfluorenyl)]zirconium dichloride, [dicyclohexylsilylene(η 5 -cyclopentadienyl)(η 5 -Octamethyloctahydrodibenzofluorenyl)]zirconium dichloride, [dicyclohexylsilylene(η 5 -cyclopentadienyl)(η 5 -tetramethyloctahydrodibenzofluorenyl)]zirconium dichloride, [Ethylene(η 5 -cyclopentadienyl)(η 5 -fluorenyl)]zirconium dichloride, [ethylene(η 5 -cyclopentadienyl)(η 5 -2,7-di-t-butylfluorenyl)]zirconium dichloride, [ethylene(η 5 -cyclopentadienyl)(η 5 -3,6-di-t-butylfluorenyl)]zirconium dichloride, [ethylene(η 5 -cyclopentadienyl)(η 5 -octamethyloctahydrodibenzofluorenyl)]zirconium dichloride, [ethylene(η 5 -cyclopentadienyl)(η 5-tetramethyloctahydrodibenzofluorenyl)]zirconium dichloride, Ethylene [η 5 -(3-tert-butyl-5-methylcyclopentadienyl)](η 5 -Fluorenyl)zirconium dichloride, ethylene [η 5 -(3-tert-butyl-5-methylcyclopentadienyl)][η 5 -(3,6-di-tert-butylfluorenyl)]zirconium dichloride, ethylene [η 5 -(3-tert-butyl-5-methylcyclopentadienyl)][η 5 -(2,7-di-tert-butylfluorenyl)]zirconium dichloride, ethylene [η 5 -(3-tert-butyl-5-methylcyclopentadienyl)](octamethyloctahydrodibenzfluorenyl)zirconium dichloride, ethylene [η 5 -(3-tert-butyl-5-methylcyclopentadienyl)](benzofluorenyl)zirconium dichloride, ethylene [η 5 -(3-tert-butyl-5-methylcyclopentadienyl)](dibenzofluorenyl)zirconium dichloride, ethylene [η 5 -(3-tert-butyl-5-methylcyclopentadienyl)](octahydrodibenzofluorenyl)zirconium dichloride, ethylene [η 5 -(3-tert-butyl-5-methylcyclopentadienyl)][η 5 -(2,7-diphenyl-3,6-di-tert-butylfluorenyl)]zirconium dichloride, ethylene [η 5 -(3-tert-butyl-5-methylcyclopentadienyl)][η 5 -(2,7-dimethyl-3,6-di-tert-butylfluorenyl)]zirconium dichloride, Ethylene [η 5 -(3-tert-butylcyclopentadienyl)](η 5 -Fluorenyl)zirconium dichloride, ethylene [η 5 -(3-tert-Butylcyclopentadienyl)][η5 -(3,6-di-tert-butylfluorenyl)]zirconium dichloride, ethylene [η 5 -(3-tert-Butylcyclopentadienyl)][η 5 -(2,7-di-tert-butylfluorenyl)]zirconium dichloride, ethylene [η 5 -(3-tert-butylcyclopentadienyl)](octamethyloctahydrodibenzfluorenyl)zirconium dichloride, ethylene [η 5 -(3-tert-butylcyclopentadienyl)](benzofluorenyl)zirconium dichloride, ethylene [η 5 -(3-tert-butylcyclopentadienyl)](dibenzofluorenyl)zirconium dichloride, ethylene [η 5 -(3-tert-butylcyclopentadienyl)](octahydrodibenzofluorenyl)zirconium dichloride, ethylene [η 5 -(3-tert-Butylcyclopentadienyl)][η 5 -(2,7-diphenyl-3,6-di-tert-butylfluorenyl)]zirconium dichloride, ethylene [η 5 -(3-tert-Butylcyclopentadienyl)][η 5 -(2,7-dimethyl-3,6-di-tert-butylfluorenyl)]zirconium dichloride, Ethylene [η 5 -(3-n-butylcyclopentadienyl)](η 5 -Fluorenyl)zirconium dichloride, ethylene [η 5 -(3-n-butylcyclopentadienyl)][η 5 -(3,6-di-tert-butylfluorenyl)]zirconium dichloride, ethylene [η 5 -(3-n-butylcyclopentadienyl)][η 5 -(2,7-di-tert-butylfluorenyl)]zirconium dichloride, ethylene [η 5 -(3-n-butylcyclopentadienyl)](octamethyloctahydrodibenzfluorenyl)zirconium dichloride, ethylene [η 5-(3-n-butylcyclopentadienyl)](benzofluorenyl)zirconium dichloride, ethylene [η 5 -(3-n-butylcyclopentadienyl)](dibenzofluorenyl)zirconium dichloride, ethylene [η 5 -(3-n-butylcyclopentadienyl)](octahydrodibenzofluorenyl)zirconium dichloride, ethylene [η 5 -(3-n-butylcyclopentadienyl)][η 5 -(2,7-diphenyl-3,6-di-tert-butylfluorenyl)]zirconium dichloride, ethylene [η 5 -(3-n-butylcyclopentadienyl)][η 5 -(2,7-dimethyl-3,6-di-tert-butylfluorenyl)]zirconium dichloride, Diphenylmethylene [η 5 -(3-tert-butyl-5-methylcyclopentadienyl)](η 5 -Fluorenyl)zirconium dichloride, diphenylmethylene [η 5 -(3-tert-butyl-5-methylcyclopentadienyl)][η 5 -(3,6-di-tert-butylfluorenyl)]zirconium dichloride, diphenylmethylene [η 5 -(3-tert-butyl-5-methylcyclopentadienyl)][η 5 -(2,7-di-tert-butylfluorenyl)]zirconium dichloride, diphenylmethylene [η 5 -(3-tert-butyl-5-methylcyclopentadienyl)](octamethyloctahydrodibenzfluorenyl)zirconium dichloride, diphenylmethylene [η 5 -(3-tert-butyl-5-methylcyclopentadienyl)](benzofluorenyl)zirconium dichloride, diphenylmethylene [η 5 -(3-tert-butyl-5-methylcyclopentadienyl)](dibenzofluorenyl)zirconium dichloride, diphenylmethylene [η 5-(3-tert-butyl-5-methylcyclopentadienyl)](octahydrodibenzofluorenyl)zirconium dichloride, diphenylmethylene [η 5 -(3-tert-butyl-5-methylcyclopentadienyl)][η 5 -(2,7-diphenyl-3,6-di-tert-butylfluorenyl)]zirconium dichloride, diphenylmethylene [η 5 -(3-tert-butyl-5-methylcyclopentadienyl)][η 5 -(2,7-dimethyl-3,6-di-tert-butylfluorenyl)]zirconium dichloride, Diphenylmethylene [η 5 -(3-tert-butylcyclopentadienyl)](η 5 -Fluorenyl)zirconium dichloride, diphenylmethylene [η 5 -(3-tert-Butylcyclopentadienyl)][η 5 -(3,6-di-tert-butylfluorenyl)]zirconium dichloride, diphenylmethylene [η 5 -(3-tert-Butylcyclopentadienyl)][η 5 -(2,7-di-tert-butylfluorenyl)]zirconium dichloride, diphenylmethylene [η 5 -(3-tert-butylcyclopentadienyl)](octamethyloctahydrodibenzfluorenyl)zirconium dichloride, diphenylmethylene [η 5 -(3-tert-butylcyclopentadienyl)](benzofluorenyl)zirconium dichloride, diphenylmethylene [η 5 -(3-tert-butylcyclopentadienyl)](dibenzofluorenyl)zirconium dichloride, diphenylmethylene [η 5 -(3-tert-butylcyclopentadienyl)](octahydrodibenzofluorenyl)zirconium dichloride, diphenylmethylene [η 5 -(3-tert-Butylcyclopentadienyl)][η 5-(2,7-diphenyl-3,6-di-tert-butylfluorenyl)]zirconium dichloride, diphenylmethylene [η 5 -(3-tert-Butylcyclopentadienyl)][η 5 -(2,7-dimethyl-3,6-di-tert-butylfluorenyl)]zirconium dichloride, Diphenylmethylene [η 5 -(3-n-butylcyclopentadienyl)](η 5 -Fluorenyl)zirconium dichloride, diphenylmethylene [η 5 -(3-n-butylcyclopentadienyl)][η 5 -(3,6-di-tert-butylfluorenyl)]zirconium dichloride, diphenylmethylene [η 5 -(3-n-butylcyclopentadienyl)][η 5 -(2,7-di-tert-butylfluorenyl)]zirconium dichloride, diphenylmethylene [η 5 -(3-n-butylcyclopentadienyl)](octamethyloctahydrodibenzfluorenyl)zirconium dichloride, diphenylmethylene [η 5 -(3-n-butylcyclopentadienyl)](benzofluorenyl)zirconium dichloride, diphenylmethylene [η 5 -(3-n-butylcyclopentadienyl)](dibenzofluorenyl)zirconium dichloride, diphenylmethylene [η 5 -(3-n-butylcyclopentadienyl)](octahydrodibenzofluorenyl)zirconium dichloride, diphenylmethylene [η 5 -(3-n-butylcyclopentadienyl)][η 5 -(2,7-diphenyl-3,6-di-tert-butylfluorenyl)]zirconium dichloride, diphenylmethylene [η 5 -(3-n-butylcyclopentadienyl)][η 5 -(2,7-dimethyl-3,6-di-tert-butylfluorenyl)]zirconium dichloride, Di(p-tolyl)methylene [η 5-(3-tert-butyl-5-methylcyclopentadienyl)](η 5 -Fluorenyl)zirconium dichloride, di(p-tolyl)methylene [η 5 -(3-tert-butyl-5-methylcyclopentadienyl)][η 5 -(3,6-di-tert-butylfluorenyl)]zirconium dichloride, di(p-tolyl)methylene [η 5 -(3-tert-butyl-5-methylcyclopentadienyl)][η 5 -(2,7-di-tert-butylfluorenyl)]zirconium dichloride, di(p-tolyl)methylene [η 5 -(3-tert-butyl-5-methylcyclopentadienyl)](octamethyloctahydrodibenzfluorenyl)zirconium dichloride, di(p-tolyl)methylene [η 5 -(3-tert-butyl-5-methylcyclopentadienyl)](benzofluorenyl)zirconium dichloride, di(p-tolyl)methylene [η 5 -(3-tert-butyl-5-methylcyclopentadienyl)](dibenzofluorenyl)zirconium dichloride, di(p-tolyl)methylene [η 5 -(3-tert-butyl-5-methylcyclopentadienyl)](octahydrodibenzofluorenyl)zirconium dichloride, di(p-tolyl)methylene [η 5 -(3-tert-butyl-5-methylcyclopentadienyl)][η 5 -(2,7-diphenyl-3,6-di-tert-butylfluorenyl)]zirconium dichloride, di(p-tolyl)methylene [η 5 -(3-tert-butyl-5-methylcyclopentadienyl)][η 5 -(2,7-dimethyl-3,6-di-tert-butylfluorenyl)]zirconium dichloride, Di(p-tolyl)methylene [η 5 -(3-tert-butylcyclopentadienyl)](η 5 -Fluorenyl)zirconium dichloride, di(p-tolyl)methylene [η 5-(3-tert-Butylcyclopentadienyl)][η 5 -(3,6-di-tert-butylfluorenyl)]zirconium dichloride, di(p-tolyl)methylene [η 5 -(3-tert-Butylcyclopentadienyl)][η 5 -(2,7-di-tert-butylfluorenyl)]zirconium dichloride, di(p-tolyl)methylene [η 5 -(3-tert-butylcyclopentadienyl)](octamethyloctahydrodibenzfluorenyl)zirconium dichloride, di(p-tolyl)methylene [η 5 -(3-tert-butylcyclopentadienyl)](benzofluorenyl)zirconium dichloride, di(p-tolyl)methylene [η 5 -(3-tert-butylcyclopentadienyl)](dibenzofluorenyl)zirconium dichloride, di(p-tolyl)methylene [η 5 -(3-tert-butylcyclopentadienyl)](octahydrodibenzofluorenyl)zirconium dichloride, di(p-tolyl)methylene [η 5 -(3-tert-Butylcyclopentadienyl)][η 5 -(2,7-diphenyl-3,6-di-tert-butylfluorenyl)]zirconium dichloride, di(p-tolyl)methylene [η 5 -(3-tert-Butylcyclopentadienyl)][η 5 -(2,7-dimethyl-3,6-di-tert-butylfluorenyl)]zirconium dichloride, Di(p-tolyl)methylene [η 5 -(3-n-butylcyclopentadienyl)](η 5 -Fluorenyl)zirconium dichloride, di(p-tolyl)methylene [η 5 -(3-n-butylcyclopentadienyl)][η 5 -(3,6-di-tert-butylfluorenyl)]zirconium dichloride, di(p-tolyl)methylene [η 5 -(3-n-butylcyclopentadienyl)][η 5-(2,7-di-tert-butylfluorenyl)]zirconium dichloride, di(p-tolyl)methylene [η 5 -(3-n-butylcyclopentadienyl)](octamethyloctahydrodibenzfluorenyl)zirconium dichloride, di(p-tolyl)methylene [η 5 -(3-n-butylcyclopentadienyl)](benzofluorenyl)zirconium dichloride, di(p-tolyl)methylene [η 5 -(3-n-butylcyclopentadienyl)](dibenzofluorenyl)zirconium dichloride, di(p-tolyl)methylene [η 5 -(3-n-butylcyclopentadienyl)](octahydrodibenzofluorenyl)zirconium dichloride, di(p-tolyl)methylene [η 5 -(3-n-butylcyclopentadienyl)](2,7-diphenyl-3,6-di-tert-butylfluorenyl)zirconium dichloride, di(p-tolyl)methylene [η 5 -(3-n-butylcyclopentadienyl)][η 5 -(2,7-dimethyl-3,6-di-tert-butylfluorenyl)]zirconium dichloride etc.

[0085] Examples of the bridged metallocene compound (P) include compounds in which the zirconium atom of the above-mentioned compound is replaced with a hafnium atom or a titanium atom, and compounds in which the chloro ligand is replaced with a methyl group. 5 -Tetramethyloctahydrodibenzofluorenyl is 4,4,7,7-tetramethyl-(5a,5b,11a,12,12a-η 5 )-1,2,3,4,7,8,9,10-octahydrodibenzo[b,H]fluorenyl group, η 5 -Octamethyloctahydrodibenzofluorenyl is 1,1,4,4,7,7,10,10-octamethyl-(5a,5b,11a,12,12a-η 5 )-1,2,3,4,7,8,9,10-octahydrodibenzo[b,H]fluorenyl group, respectively. The crosslinked metallocene compound (P) may be used alone or in combination of two or more kinds.

[0086] [Compound (Q)] Compound (Q) is at least one compound selected from the group consisting of an organometallic compound (Q-1), an organoaluminum oxy compound (Q-2), and a compound (Q-3) that reacts with the crosslinked metallocene compound (P) to form an ion pair. Specific examples of the organometallic compound (Q-1) include organometallic compounds (Q-1a), (Q-1b), and (Q-1c) of Groups 1, 2, 12, and 13 of the periodic table as follows.

[0087] (Q-1a) General formula R a m Al(OR b ) n H p X q An organoaluminum compound represented by the formula. (In the formula, R a and R b may be the same or different from each other and represent a hydrocarbon group having 1 to 15 carbon atoms, preferably 1 to 4 carbon atoms, X represents a halogen atom, m is a number where 0 < m ≦ 3, n is a number where 0 ≦ n < 3, p is a number where 0 ≦ p < 3, q is a number where 0 ≦ q < 3, and m + n + p + q = 3) Examples of such compounds include tri-n-alkylaluminums such as trimethylaluminum, triethylaluminum, tri-n-butylaluminum, tri-n-hexylaluminum, and tri-n-octylaluminum; tri-branched alkylaluminums such as triisopropylaluminum, triisobutylaluminum, trisec-butylaluminum, tri-t-butylaluminum, tri-2-methylbutylaluminum, tri-3-methylhexylaluminum, and tri-2-ethylhexylaluminum; tricycloalkylaluminums such as tricyclohexylaluminum and tricyclooctylaluminum; triarylaluminums such as triphenylaluminum and tri(4-methylphenyl)aluminum; dialkylaluminum hydrides such as diisopropylaluminum hydride and diisobutylaluminum hydride; and compounds represented by the general formula (i-C4H9) x Al y (C5H 10 ) z (wherein x, y, and z are positive numbers, and z≦2x), alkenyl aluminum such as isoprenyl aluminum, alkyl aluminum alkoxides such as isobutyl aluminum methoxide and isobutyl aluminum ethoxide, dialkyl aluminum alkoxides such as dimethyl aluminum methoxide, diethyl aluminum ethoxide, and dibutyl aluminum butoxide, alkyl aluminum sesquialkoxides such as ethyl aluminum sesquiethoxide and butyl aluminum sesquibutoxide, and alkyl aluminum sesquialkoxides represented by the general formula R a 2.5 Al(OR b ) 0.5Examples of the alkylaluminum include partially alkoxylated alkylaluminums having an average composition represented by the formula (I) above, alkylaluminum aryloxides such as diethylaluminum phenoxide and diethylaluminum (2,6-di-t-butyl-4-methylphenoxide), dialkylaluminum halides such as dimethylaluminum chloride, diethylaluminum chloride, dibutylaluminum chloride, diethylaluminum bromide and diisobutylaluminum chloride, alkylaluminum sesquihalides such as ethylaluminum sesquichloride, butylaluminum sesquichloride and ethylaluminum sesquibromide, partially halogenated alkylaluminums such as alkylaluminum dihalides represented by ethylaluminum dichloride, dialkylaluminum hydrides such as diethylaluminum hydride and dibutylaluminum hydride, alkylaluminum dihydrides such as ethylaluminum dihydride and propylaluminum dihydride, and other partially hydrogenated alkylaluminums, partially alkoxylated and halogenated alkylaluminums such as ethylaluminum ethoxy chloride, butylaluminum butoxy chloride and ethylaluminum ethoxy bromide. a m Al(OR b ) n H p X q Compounds similar to the compound represented by the formula (1) can also be used, such as organoaluminum compounds in which two or more aluminum compounds are bonded via nitrogen atoms. Specific examples of such compounds include (C2H5)2AlN(C2H5)Al(C2H5)2.

[0088] (Q-1b) General formula M 2 AlR a 4, a complex alkylation product of a Group 1 metal of the Periodic Table and aluminum. (Wherein, M 2 indicates Li, Na or K, and R a represents a hydrocarbon group having 1 to 15 carbon atoms, preferably 1 to 4 carbon atoms. Such compounds include LiAl(C2H5)4, LiAl(C7H 15 ) 4 can be given as an example.

[0089] (Q-1c) General formula R a R b M 3 A dialkyl compound of a metal of Group 2 or 12 of the periodic table represented by the formula: a and R b may be the same or different and each represents a hydrocarbon group having 1 to 15 carbon atoms, preferably 1 to 4 carbon atoms; M 3 is Mg, Zn or Cd.) As the organoaluminum oxy compound (Q-2), a conventionally known aluminoxane can be used as it is.Specific examples include a compound represented by the following general formula [III] and a compound represented by the following general formula [IV].

[0090] [ka] In the formulas [III] and [IV], R represents a hydrocarbon group having 1 to 10 carbon atoms, and n represents an integer of 2 or more.

[0091] In particular, methylaluminoxanes are used in which R is a methyl group and n is at least 3, preferably at least 10. There is no problem if these aluminoxanes contain a small amount of an organoaluminum compound.

[0092] In the present invention, when copolymerization of ethylene with an α-olefin having 3 or more carbon atoms is carried out at high temperature, a benzene-insoluble organoaluminum oxy compound as exemplified in JP-A-2-78687 can also be used. In addition, an organoaluminum oxy compound described in JP-A-2-167305, an aluminoxane having two or more alkyl groups described in JP-A-2-24701 and JP-A-3-103407, etc. can also be suitably used. Note that the "benzene-insoluble organoaluminum oxy compound" that may be used in one embodiment of the present invention is a compound that is insoluble or poorly soluble in benzene, and that has an Al component that dissolves in benzene at 60°C in terms of Al atom is usually 10% or less, preferably 5% or less, and particularly preferably 2% or less.

[0093] Further, the organoaluminum oxy compound (Q-2) may also include modified methylaluminoxanes as represented by the following general formula [V].

[0094] [ka] In formula [V], R represents a hydrocarbon group having 1 to 10 carbon atoms, and m and n each independently represent an integer of 2 or more.

[0095] Methylaluminoxane, an example of an organoaluminum oxy compound (Q-2), is commonly used as an activator in polyolefin polymerization because it is readily available and has high polymerization activity. However, methylaluminoxane is difficult to dissolve in saturated hydrocarbons, so it has been used as a solution in aromatic hydrocarbons such as toluene or benzene, which are environmentally undesirable. For this reason, in recent years, a flexible body of methylaluminoxane represented by formula [IV] has been developed and used as an aluminoxane dissolved in saturated hydrocarbons. This modified methylaluminoxane represented by formula [V] is prepared using trimethylaluminum and alkylaluminum other than trimethylaluminum, for example, trimethylaluminum and triisobutylaluminum, as shown in, for example, U.S. Pat. No. 4,960,878 and U.S. Pat. No. 5,041,584. Aluminoxanes in which Rx is an isobutyl group are commercially available in the form of saturated hydrocarbon solutions under the trade names MMAO and TMAO (see Tosoh Finechem Corporation, Tosoh Research & Technology Review, Vol. 47, 55 (2003)).

[0096] Further, the organoaluminum oxy compound (Q-2) may also include a boron-containing organoaluminum oxy compound represented by the following general formula [VI].

[0097] [ka] In formula [VI], R c R represents a hydrocarbon group having 1 to 10 carbon atoms. d may be the same or different and represent a hydrogen atom, a halogen atom, or a hydrocarbon group having 1 to 10 carbon atoms.

[0098] Examples of the compound (Q-3) that reacts with the bridged metallocene compound (P) to form an ion pair (hereinafter sometimes abbreviated as "ionized ionic compound" or simply "ionic compound") include Lewis acids, ionic compounds, borane compounds, and carborane compounds described in JP-A-1-501950, JP-A-1-502036, JP-A-3-179005, JP-A-3-179006, JP-A-3-207703, JP-A-3-207704, and U.S. Patent No. 5,321,106. Further examples include heteropoly compounds and isopoly compounds.

[0099] In one embodiment of the present invention, the ionizing ionic compound preferably used is a boron compound represented by the following general formula [VII].

[0100] [ka] In formula [VII], R e+ As for H + , carbenium cation, oxonium cation, ammonium cation, phosphonium cation, cycloheptyltrienyl cation, ferrocenium cation having a transition metal, etc. f ~R i may be the same or different and are substituents selected from a hydrocarbon group having 1 to 20 carbon atoms, a silicon-containing group, a nitrogen-containing group, an oxygen-containing group, a halogen atom and a halogen-containing group, and are preferably substituted aryl groups.

[0101] Specific examples of the carbenium cation include tri-substituted carbenium cations such as triphenylcarbenium cation, tris(4-methylphenyl)carbenium cation, and tris(3,5-dimethylphenyl)carbenium cation.

[0102] Specific examples of the ammonium cation include trialkyl-substituted ammonium cations such as trimethylammonium cation, triethylammonium cation, tri(n-propyl)ammonium cation, triisopropylammonium cation, tri(n-butyl)ammonium cation, and triisobutylammonium cation; N,N-dialkylanilinium cations such as N,N-dimethylanilinium cation, N,N-diethylanilinium cation, and N,N-2,4,6-pentamethylanilinium cation; and dialkylammonium cations such as diisopropylammonium cation and dicyclohexylammonium cation.

[0103] Specific examples of the phosphonium cation include triarylphosphonium cations such as triphenylphosphonium cation, tris(4-methylphenyl)phosphonium cation, and tris(3,5-dimethylphenyl)phosphonium cation.

[0104] R e+ Of the above specific examples, preferred are carbenium cations and ammonium cations, with triphenylcarbenium cation, N,N-dimethylanilinium cation and N,N-diethylanilinium cation being particularly preferred.

[0105] Among the ionized ionic compounds preferably used in one embodiment of the present invention, examples of compounds containing a carbenium cation include triphenylcarbenium tetraphenylborate, triphenylcarbenium tetrakis(pentafluorophenyl)borate, triphenylcarbenium tetrakis{3,5-di-(trifluoromethyl)phenyl}borate, tris(4-methylphenyl)carbenium tetrakis(pentafluorophenyl)borate, and tris(3,5-dimethylphenyl)carbenium tetrakis(pentafluorophenyl)borate.

[0106] Among the ionizing ionic compounds preferably used in one embodiment of the present invention, compounds containing a trialkyl-substituted ammonium cation include triethylammonium tetraphenylborate, tripropylammonium tetraphenylborate, tri(n-butyl)ammonium tetraphenylborate, trimethylammonium tetrakis(4-methylphenyl)borate, trimethylammonium tetrakis(2-methylphenyl)borate, tri(n-butyl)ammonium tetrakis(pentafluorophenyl)borate, triethylammonium tetrakis(pentafluorophenyl)borate, tripropyl ... rakis(pentafluorophenyl)borate, tripropylammonium tetrakis(2,4-dimethylphenyl)borate, tri(n-butyl)ammonium tetrakis(3,5-dimethylphenyl)borate, tri(n-butyl)ammonium tetrakis{4-(trifluoromethyl)phenyl}borate, tri(n-butyl)ammonium tetrakis{3,5-di(trifluoromethyl)phenyl}borate, tri(n-butyl)ammonium tetrakis(2-methylphenyl)borate, dioctadecylmethylammonium tetraphenylborate, dioctadecylmethylammonium tetrakis(4-methylphenyl)borate , J Examples of the tetrakis include octadecylmethylammonium tetrakis(pentafluorophenyl)borate, dioctadecylmethylammonium tetrakis(2,4-dimethylphenyl)borate, dioctadecylmethylammonium tetrakis(3,5-dimethylphenyl)borate, dioctadecylmethylammonium tetrakis{4-(trifluoromethyl)phenyl}borate, dioctadecylmethylammonium tetrakis{3,5-di(trifluoromethyl)phenyl}borate, and dioctadecylmethylammonium.

[0107] Among the ionized ionic compounds preferably used in one embodiment of the present invention, examples of compounds containing an N,N-dialkylanilinium cation include N,N-dimethylanilinium tetraphenylborate, N,N-dimethylanilinium tetrakis(pentafluorophenyl)borate, N,N-dimethylanilinium tetrakis{3,5-di(trifluoromethyl)phenyl}borate, N,N-diethylanilinium tetraphenylborate, N,N-diethylanilinium tetrakis(pentafluorophenyl)borate, N,N-diethylanilinium tetrakis{3,5-di(trifluoromethyl)phenyl}borate, N,N-2,4,6-pentamethylanilinium tetraphenylborate, and N,N-2,4,6-pentamethylanilinium tetrakis(pentafluorophenyl)borate.

[0108] Among the ionized ionic compounds preferably used in one embodiment of the present invention, examples of compounds containing a dialkylammonium cation include di-n-propylammonium tetrakis(pentafluorophenyl)borate and dicyclohexylammonium tetraphenylborate.

[0109] In addition, the ionic compounds exemplified in JP-A-2004-51676 can also be used without any restrictions. The above ionic compounds (Q-3) may be used alone or in combination of two or more.

[0110] Examples of the catalyst system include the following [1] to [4]. [1] Bridged metallocene compound (P) and compound (Q-2) [2] Includes bridged metallocene compound (P), compound (Q-1) and compound (Q-2) [3] Bridged metallocene compound (P), compound (Q-1) and compound (Q-3) are included. [4] Includes bridged metallocene compound (P), compound (Q-2) and compound (Q-3) The bridged metallocene compound (P) and the compounds (Q-1) to (Q-3) may be introduced into the reaction system in any order.

[0111] [Carrier (R)] In one embodiment of the present invention, a support (R) may be used as a constituent component of the olefin polymerization catalyst, if necessary.

[0112] The carrier (R) that may be used in one embodiment of the present invention is an inorganic or organic compound, and is a granular or particulate solid. Among these, the inorganic compound is preferably a porous oxide, an inorganic chloride, a clay, a clay mineral, or an ion-exchangeable layered compound.

[0113] Specifically, the porous oxide may be SiO2, Al2O3, MgO, ZrO, TiO2, B2O3, CaO, ZnO, BaO, ThO2, or a composite or mixture containing these, such as natural or synthetic zeolite, SiO2-MgO, SiO2-Al2O3, SiO2-TiO2, SiO2-V2O5, SiO2-Cr2O3, SiO2-TiO2-MgO, or the like. Among these, those containing SiO2 and / or Al2O3 as the main component are preferred. The properties of such porous oxides vary depending on the type and manufacturing method, but the carrier preferably used in one embodiment of the present invention has a particle size of 0.5 to 300 μm, preferably 1.0 to 200 μm, and a specific surface area of ​​50 to 1,000 m. 2 / g, preferably 100 to 700m 2 / g and the pore volume is 0.3-3.0 cm 3 The carrier is preferably calcined at 100 to 1,000° C., and more preferably at 150 to 700° C., if necessary, before use.

[0114] Examples of inorganic chlorides that can be used include MgCl2, MgBr2, MnCl2, and MnBr2. The inorganic chlorides can be used as they are, or can be used after being pulverized by a ball mill or a vibration mill. In addition, the inorganic chlorides can be dissolved in a solvent such as alcohol, and then precipitated into fine particles using a precipitating agent.

[0115] Clay is usually composed of clay minerals as the main component. In addition, an ion-exchangeable layered compound is a compound having a crystal structure in which the constituent faces are stacked in parallel with each other with weak bonding force due to ionic bonds, etc., and the ions contained therein are exchangeable. Most clay minerals are ion-exchangeable layered compounds. In addition, these clays, clay minerals, and ion-exchangeable layered compounds are not limited to natural products, and artificial synthetic products can also be used. In addition, examples of clays, clay minerals, and ion-exchangeable layered compounds include clays, clay minerals, and ionic crystalline compounds having layered crystal structures such as hexagonal close packing type, antimony type, CdCl2 type, and CdI2 type. Examples of such clays and clay minerals include kaolin, bentonite, kibushi clay, gairome clay, allophane, hisingerite, pyrophyllite, ummo group, montmorillonite group, vermiculite, ryokudeite group, palygorskite, kaolinite, nacrite, dickite, and halloysite, and examples of ion-exchangeable layered compounds include α-Zr(HAsO4)2·H2O, α-Zr(HPO4)2, α-Zr(KPO4)2·3H2O, α-Ti(HPO4)2, α-Ti(HAsO4)2·H2O, α-Sn(HPO4)2·H2O, γ-Zr(HPO4)2, γ-Ti(HPO4)2, and γ-Ti(NH4PO4)2·H2O, and other crystalline acid salts of polyvalent metals. It is also preferable to subject the clay and clay minerals used in one embodiment of the present invention to chemical treatment. The chemical treatment may be any of surface treatments that remove impurities adhering to the surface, treatments that affect the crystal structure of the clay, etc. Specific examples of the chemical treatment include acid treatment, alkali treatment, salt treatment, and organic matter treatment.

[0116] The ion-exchangeable layered compound may be a layered compound in which the space between layers is expanded by utilizing the ion exchangeability and exchanging the exchangeable ions between layers with other large bulky ions. Such bulky ions play a role of supporting the layered structure and are usually called pillars. The introduction of another substance (guest compound) between layers of a layered compound in this way is called intercalation. Examples of guest compounds include cationic inorganic compounds such as TiCl4 and ZrCl4, metal alkoxides such as Ti(OR)4, Zr(OR)4, PO(OR)3, and B(OR)3 (R is a hydrocarbon group, etc.), [Al 13 O4(OH) 24 ] 7+ , [Zr4(OH) 14 ] 2+ , [Fe3O(OCOCH3)6] + Metal hydroxide ions such as these can be used. These compounds can be used alone or in combination of two or more. When these compounds are intercalated, polymers obtained by hydrolysis and polycondensation of metal alkoxides such as Si(OR)4, Al(OR)3, Ge(OR)4 (R is a hydrocarbon group, etc.), colloidal inorganic compounds such as SiO2, etc. can also be coexisted. Examples of pillars include oxides produced by intercalating the above metal hydroxide ions between layers and then dehydrating them with heat.

[0117] Of these, clay or clay minerals are preferred, and montmorillonite, vermiculite, pectolite, taeniolite and synthetic mica are particularly preferred. The organic compound as the carrier (R) may be a granular or fine particle solid having a particle size in the range of 0.5 to 300 μm. Specifically, it may be a (co)polymer produced mainly from an α-olefin having 2 to 14 carbon atoms, such as ethylene, propylene, 1-butene, or 4-methyl-1-pentene, or a (co)polymer produced mainly from vinylcyclohexane or styrene, or a modified product thereof.

[0118] The method of use and order of addition of each component of the polymerization catalyst may be selected arbitrarily, and at least two of the components in the catalyst may be contacted in advance. The bridged metallocene compound (P) (hereinafter also referred to as "component (P)") is usually 10 -9 ~10 -1 mol, preferably 10 -8 ~10 -2 It is used in amounts that equal mol.

[0119] The organometallic compound (Q-1) (hereinafter also referred to as "component (Q-1)") is used in an amount such that the molar ratio of component (Q-1) to the transition metal atom (M) in component (P) [(Q-1) / M] is generally 0.01 to 50,000, preferably 0.05 to 10,000.

[0120] The organoaluminum oxy compound (Q-2) (hereinafter also referred to as "component (Q-2)") is used in an amount such that the molar ratio [(Q-2) / M] of the aluminum atom in component (Q-2) to the transition metal atom (M) in component (P) is generally 10 to 5,000, preferably 20 to 2,000.

[0121] The ionic compound (Q-3) (hereinafter also referred to as "component (Q-3)") is used in an amount such that the molar ratio of component (Q-3) to the transition metal atom (M) in component (P) [(Q-3) / M] is generally 1 to 10,000, preferably 1 to 5,000.

[0122] The polymerization temperature is usually -50°C to 300°C, preferably 30 to 250°C, more preferably 100°C to 250°C, and further preferably 130°C to 200°C. In the polymerization temperature range, as the temperature increases, the solution viscosity during polymerization decreases and the heat of polymerization is easily removed. The polymerization pressure is usually normal pressure to 10 MPa gauge pressure (MPa-G), preferably normal pressure to 8 MPa-G. The polymerization reaction can be carried out by any of a batch method, a semi-continuous method, and a continuous method. Furthermore, the polymerization can be carried out continuously in two or more polymerization vessels with different reaction conditions.

[0123] The molecular weight of the resulting copolymer can be adjusted by changing the hydrogen concentration in the polymerization system or the polymerization temperature. It can also be adjusted by the amount of component (Q) used. When hydrogen is added, the amount is appropriately about 0.001 to 5,000 NL per kg of the resulting copolymer.

[0124] The polymerization solvent used in the liquid phase polymerization method is usually an inert hydrocarbon solvent, preferably a saturated hydrocarbon having a boiling point of 50°C to 200°C under normal pressure. Specific examples of the polymerization solvent include aliphatic hydrocarbons such as propane, butane, pentane, hexane, heptane, octane, decane, dodecane, and kerosene, and alicyclic hydrocarbons such as cyclopentane, cyclohexane, and methylcyclopentane, and particularly preferably hexane, heptane, octane, decane, and cyclohexane. The α-olefin itself, which is the object of polymerization, can also be used as the polymerization solvent. Incidentally, aromatic hydrocarbons such as benzene, toluene, and xylene, and halogenated hydrocarbons such as ethylene chloride, chlorobenzene, and dichloromethane can also be used as the polymerization solvent, but from the viewpoint of reducing the burden on the environment and minimizing the impact on human health, the use of these is not preferred.

[0125] In general, the kinetic viscosity of an olefin polymer at 100°C depends on the molecular weight of the polymer. That is, a high molecular weight results in a high viscosity, and a low molecular weight results in a low viscosity, so the kinetic viscosity at 100°C is adjusted by adjusting the molecular weight as described above. In addition, the molecular weight distribution (Mw / Mn) of the obtained polymer can be adjusted by removing low molecular weight components from the obtained polymer by a conventionally known method such as reduced pressure distillation. Furthermore, the obtained polymer may be hydrogenated (hereinafter also referred to as hydrogenation) by a conventionally known method. If the double bonds of the obtained polymer are reduced by hydrogenation, the oxidation stability and heat resistance are improved.

[0126] The ethylene / α-olefin copolymer (B) obtained by adjusting the molecular weight as described above may be used alone or in combination of two or more types having different molecular weights or different monomer compositions. The ethylene-α-olefin copolymer (B) according to one embodiment of the present invention may be a modified copolymer obtained by providing an ethylene-α-olefin copolymer with a substituent other than a saturated hydrocarbon group. Among these, the modified copolymer is preferably a copolymer modified with one or more compounds selected from compounds having a substituent other than a saturated hydrocarbon group and a carbon-carbon unsaturated bond, and more preferably a copolymer modified with one or more compounds selected from unsaturated carboxylic acids and their derivatives. The grafting position of the substituent is not particularly limited.

[0127] When modification is performed with one or more compounds selected from compounds having a substituent other than a saturated hydrocarbon group and having a carbon-carbon unsaturated bond, examples of the substituent other than the saturated hydrocarbon group include substituents having an aromatic ring and / or a heteroaromatic ring, such as a benzene ring, a naphthalene ring, a pyridine ring, or a thiophene ring; oxygen-containing groups, such as a carboxy group, an acid anhydride group, an ether bond, an ester bond, a hydroxy group, or an epoxy group; nitrogen-containing groups, such as an amide group, an imide bond, an amino group, a nitrile group, or an isocyanate group; sulfur-containing groups, such as a sulfinyl group, a sulfanyl group, or a sulfonyl group; and silicon-containing groups, such as a trialkylsilyl group or a trialkoxysilyl group.

[0128] Examples of compounds having a substituent other than a saturated hydrocarbon group and a carbon-carbon unsaturated bond according to one embodiment of the present invention include compounds having an aromatic ring such as styrene and allylbenzene, compounds having an acid or acid-derived group such as acid, acid anhydride, ester, amide, and imide, compounds having an oxygen-containing group such as alcohol, epoxy, and ether, compounds having a nitrogen-containing group such as amine, nitrile, and isocyanate, compounds having a sulfur-containing group such as sulfide, sulfoxide, sulfone, and sulfonamide, and compounds having a silicon-containing group such as vinylsilane, etc. Among these, compounds having an aromatic ring, compounds having an acid or an acid-derived group, and compounds having an oxygen-containing group are preferred, compounds having an acid or an acid-derived group, and compounds having an oxygen-containing group are more preferred, and unsaturated carboxylic acids and derivatives thereof are even more preferred.

[0129] Examples of unsaturated carboxylic acids include (meth)acrylic acid, maleic acid, fumaric acid, tetrahydrophthalic acid, itaconic acid, citraconic acid, crotonic acid, isocrotonic acid, and nadic acid (endo cis-bicyclo[2,2,1]hept-5-ene-2,3-dicarboxylic acid).

[0130] The derivatives of the unsaturated carboxylic acids include acid anhydrides, esters, amides and imides of the unsaturated carboxylic acids. Examples of esters of unsaturated carboxylic acids include esters and half esters such as methyl (meth)acrylate, ethyl (meth)acrylate, monoethyl maleate, diethyl maleate, monomethyl fumarate, dimethyl fumarate, monomethyl itaconic acid, and diethyl itaconic acid.

[0131] Examples of the amide of an unsaturated carboxylic acid include (meth)acrylamide, maleic acid monoamide, maleic acid diamide, maleic acid-N-monoethylamide, maleic acid-N,N-diethylamide, maleic acid-N-monobutylamide, maleic acid-N,N-dibutylamide, fumaric acid monoamide, fumaric acid diamide, fumaric acid-N-monobutylamide, and fumaric acid-N,N-dibutylamide.

[0132] Examples of imides of unsaturated carboxylic acids include maleimide, N-butylmaleimide, and N-phenylmaleimide. Among the unsaturated carboxylic acids and derivatives thereof, unsaturated dicarboxylic acids and derivatives thereof are more preferred, and maleic acid and maleic anhydride are particularly preferred from the viewpoint that by-products such as homopolymers are less likely to be produced in the reaction for producing the modified copolymer.

[0133] In addition to the above, other methods of modification include a method of reacting with a reactive gas or liquid. Examples of the reactive gas or liquid include air, oxygen, ozone, chlorine, bromine, sulfur dioxide, and sulfuryl chloride, and one or more of these can be used. Among these, oxidation reactions using air and / or oxygen, chlorination using chlorine, and chlorosulfonation reactions using sulfuryl chloride, chlorine and sulfur dioxide, chlorine and sulfuryl chloride, and chlorine, sulfur dioxide, and sulfuryl chloride are preferred. The gas used in this method may be diluted to any concentration with an inert gas such as nitrogen, argon, or carbon dioxide.

[0134] When the ethylene-α-olefin copolymer (B) is a modified copolymer, the modification amount is 0.1 to 20 mass%, preferably 0.5 to 15 mass%. In particular, when the X / Y block copolymer (A) is a modified copolymer, the modification amount of the ethylene-α-olefin copolymer within the above range has excellent compatibility with the X / Y block copolymer (A), and can easily exhibit effects such as improved sag resistance. It is also effective in suppressing bleed-out.

[0135] The modified copolymer (B) according to one embodiment of the present invention can be produced by modifying an ethylene-α-olefin copolymer by various conventionally known methods described in, for example, JP-A-61-126120 and JP 2,593,264, or by the following method (1) or (2). (1) A method in which the copolymer is charged into an extruder or batch reactor, and then a vinyl compound to be reacted or a reactive gas or liquid is added to modify the copolymer. (2) A method in which the copolymer is dissolved in a solvent and modified by adding a vinyl compound or a reactive gas or liquid.

[0136] In any of the above methods, in order to efficiently graft the vinyl compound and / or reactive gas or liquid, it is preferable to carry out the graft copolymerization in the presence of one or more radical initiators.

[0137] Examples of the radical initiator include organic peroxides and azo compounds. Examples of the organic peroxide include benzoyl peroxide, dichlorobenzoyl peroxide, dicumyl peroxide, di-tert-butyl peroxide, 2,5-dimethyl-2,5-di(tert-butylperoxy)-3-hexyne, 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane, 1,4-bis(tert-butylperoxyisopropyl)benzene, and the like. Examples of the azo compound include azobisisobutyronitrile, dimethylazoisobutyrate, and the like.

[0138] Among these, dialkyl peroxides such as dicumyl peroxide, di-tert-butyl peroxide, 2,5-dimethyl-2,5-di(tert-butylperoxy)-3-hexyne, 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane, and 1,4-bis(tert-butylperoxyisopropyl)benzene are particularly preferably used.

[0139] The amount of the radical initiator used is usually 0.001 to 5 parts by mass, preferably 0.01 to 4 parts by mass, and more preferably 0.05 to 3 parts by mass, based on 100 parts by mass of the copolymer (A) before modification.

[0140] Among these, when modification is performed by an oxidation reaction using air and / or oxygen, the reaction may be carried out in the presence of one or more selected from metals or metal salts, inorganic acids, organic acids, etc., in addition to the radical initiator, in order to promote the reaction.

[0141] Examples of the metals or metal salts include manganese acetate, cobalt acetate, manganese chloride, nickel oxide, copper, etc., examples of the inorganic acids include hydrochloric acid and nitric acid, and examples of the organic acids include formic acid, acetic acid, oxalic acid, malonic acid, maleic acid, tartaric acid, malic acid, adipic acid, citric acid, etc.

[0142] The reaction temperature in the modification reaction is usually 20 to 350° C., and preferably 60 to 300° C. When a reactive gas is used for modification, the reaction pressure is preferably normal pressure to 5 MPa.

[0143] The modified copolymer produced by the above method may be further modified by a second modification method, for example, the method described in JP-A-2008-508402.

[0144] [Polyolefin resin (C)] The polyolefin resin (C) according to one aspect of the present invention is characterized by satisfying the following requirement (C-1).

[0145] Requirement (c-1) MFR (230°C, 2.16 kg) is 0.1 to 500 g / 10 min. The polyolefin resin (C) according to one embodiment of the present invention has an MFR (230°C, 2.16 kg) of 0.1 to 500 g / 10 min, preferably 0.5 to 100 g / 10 min, and more preferably 1 to 50 g / 10 min. The polyolefin resin having an MFR (230°C, 2.16 kg) of 0.1 to 500 g / 10 min has a kinetic viscosity of 50,000 mm at 100°C. 2 / s or more, making it practically difficult to measure the kinetic viscosity at 100°C. That is, the polyolefin resin (C) according to one embodiment of the present invention usually has a kinetic viscosity of 50,000 mm 2 / s.

[0146] The MFR (230° C., 2.16 kg) of the polyolefin resin (C) in one embodiment of the present invention is a value measured at a temperature of 230° C. and a load of 2.16 kg in accordance with JIS K 7210-1. When the MFR (230° C., 2.16 kg) of the polyolefin resin (C) is within the above range, the thermoplastic elastomer composition has an excellent balance of effects for improving the moldability (fluidity) and heat resistance.

[0147] The polyolefin resin (C) according to one embodiment of the present invention is a polymer of a monomer mainly composed of olefin. As long as it satisfies the requirement (C-1), it is not particularly limited, and various known olefin polymers can be used. For example, homopolymers and copolymers of α-olefins having 2 to 20 carbon atoms, such as ethylene, propylene, 1-butene, 1-pentene, 4-methyl-1-pentene, 1-hexene, 1-heptene, 1-octene, 1-decene, 1-undecene, 1-dodecene, 1-tridecene, 1-tetradecene, 1-pentadecene, 1-hexadecene, 1-heptadecene, 1-octadecene, 1-nonadecene, and 1-eicosene, can be mentioned. Specifically, examples of such polymers include olefin polymers such as high-pressure low-density polyethylene (LDPE), linear low-density polyethylene (LLDPE), medium-density polyethylene (MDPE), high-density polyethylene (HDPE), homopolypropylene (hPP), polypropylene random copolymer (rPP), block polypropylene (bPP), poly-1-butene, poly-4-methyl-1-pentene, low-crystalline or amorphous ethylene-propylene random copolymer, ethylene-1-butene random copolymer, and propylene-1-butene random copolymer, as well as thermoplastic elastomer compositions containing two or more of these polymers, ethylene-vinyl acetate copolymer (EVA), ethylene-(meth)acrylic acid copolymer and metal salts thereof, and ethylene-cyclic olefin copolymer.

[0148] The polyolefin resin (C) may contain a non-conjugated diene as a copolymerization component of the olefin. Specific examples of the non-conjugated diene include linear non-conjugated dienes such as 1,4-hexadiene, 1,6-octadiene, 2-methyl-1,5-hexadiene, 6-methyl-1,5-heptadiene, and 7-methyl-1,6-octadiene, cyclohexadiene, dicyclopentadiene, methyltetrahydroindene, 5-vinylnorbornene, 5-ethylidene-2-norbornene, and 5-methylene-2-nodiene. Examples of the polyolefin resin include cyclic non-conjugated dienes such as cyclohexene, 5-isopropylidene-2-norbornene, and 6-chloromethyl-5-isopropenyl-2-norbornene, and trienes such as 2,3-diisopropylidene-5-norbornene, 2-ethylidene-3-isopropylidene-5-norbornene, 2-propenyl-2,2-norbornadiene, 1,3,7-octatriene, and 1,4,9-decatriene. Among them, 1,4-hexadiene and cyclic non-conjugated dienes, particularly dicyclopentadiene, 5-ethylidene-2-norbornene, and 5-vinylnorbornene, are preferably used. Furthermore, these polyolefin resins may be polymers graft-modified with polar compounds such as maleic acid and silane compounds. Among these, polymers or copolymers of α-olefins having 2 to 20 carbon atoms, preferably 2 to 10 carbon atoms, are desirable.

[0149] The polyolefin resin (C) has an intrinsic viscosity [η] measured in decalin at 135° C., which is not particularly limited, and is preferably 0.5 dl / g or more and 5 dl / g or less. If the intrinsic viscosity [η] measured in decalin at 135° C. is small, the mechanical strength of the thermoplastic elastomer composition is reduced. If the intrinsic viscosity [η] is large, the moldability is deteriorated. If the intrinsic viscosity [η] of the polyolefin resin (C) is in the above range, moldability can be ensured while maintaining mechanical strength.

[0150] Suitable examples of such polyolefin-based resins (C) include polyethylene, polypropylene, polybutene, etc., and among these, polypropylene-based resins, which are polymers or copolymers mainly composed of propylene, are particularly preferred in terms of improving the heat resistance and mechanical strength of the thermoplastic elastomer composition.

[0151] Examples of polypropylene-based resins include propylene homopolymers, copolymers of propylene with at least one monomer selected from ethylene and α-olefins having 4 to 20 carbon atoms, and impact copolymers (block polypropylene: bPP) containing a rubber component containing many structural units derived from ethylene synthesized by multistage polymerization. When the polypropylene-based resin is a copolymer, the content of structural units derived from propylene is preferably 90 mol % or more, more preferably 93 to 99 mol %.

[0152] The melting point of the polyolefin resin (C) measured by a differential scanning calorimeter (DSC) is preferably 100 to 200°C in order to impart heat resistance to the thermoplastic elastomer composition and ensure moldability, more preferably 120 to 180°C, and further preferably 140 to 170°C.

[0153] In the present invention, the melting point of the polyolefin resin (C) was measured by storing a sample at 23°C for 72 hours, then subjecting it to differential scanning calorimetry (DSC) measurement. The sample was cooled to -40°C and then heated to 200°C at a heating rate of 10°C / min. A DSC curve was then created, and the peak temperature of the endothermic peak was analyzed with reference to JIS K 7121 to determine the melting point Tm.

[0154] As the polyolefin resin (C) according to one aspect of the present invention, two or more polyolefin resins differing in type or properties such as MFR may be used in combination.

[0155] [Thermoplastic elastomer composition] A thermoplastic elastomer composition according to one embodiment of the present invention is a composition containing the above-mentioned X / Y block copolymer (A) and ethylene-α-olefin copolymer (B), and may further contain a polyolefin resin (C).

[0156] In the thermoplastic elastomer composition according to one embodiment of the present invention, the content of the ethylene-α-olefin copolymer (B) relative to 100 parts by mass of the X / Y block copolymer (A) is 1 to 400 parts by mass, preferably 10 to 350 parts by mass, more preferably 30 to 300 parts by mass, and even more preferably 30 to 250 parts by mass. When the content of the ethylene-α-olefin copolymer (B) relative to 100 parts by mass of the X / Y block copolymer (A) is within the above range, the thermoplastic elastomer composition exhibits excellent rubber elasticity due to its softening effect and bleed-out resistance in a well-balanced manner.

[0157] In the thermoplastic elastomer composition according to one embodiment of the present invention, the content ratio of the polyolefin resin (C) relative to 100 parts by mass of the X / Y block copolymer (A) is 0 to 200 parts by mass, preferably 10 to 150 parts by mass, and more preferably 15 to 100 parts by mass. When the content of the polyolefin resin (C) relative to 100 parts by mass of the X / Y block copolymer (A) is within the above range, the thermoplastic elastomer composition is excellent in heat resistance, mechanical strength, moldability, and rubber elasticity in a well-balanced manner, which is preferable.

[0158] The thermoplastic elastomer composition according to one embodiment of the present invention may contain components other than the above (A), (B), and (C) to the extent that the object of the present invention is not impaired. Examples of components that may be contained in the thermoplastic elastomer composition of the present invention include resin components other than the above (A), (B), and (C), weather resistance stabilizers, heat resistance stabilizers, antioxidants, ultraviolet absorbers, antistatic agents, antislip agents, antiblocking agents, antifogging agents, nucleating agents, lubricants, pigments, dyes, antioxidants, hydrochloric acid absorbers, inorganic or organic fillers, organic or inorganic foaming agents, crosslinking agents, co-crosslinking agents, crosslinking assistants, adhesives, softeners, and flame retardants.

[0159] The filler is preferably an inorganic filler, and examples thereof include powder fillers such as mica, carbon black, silica, calcium carbonate, talc, graphite, stainless steel, and aluminum, and fibrous fillers such as glass fiber and metal fiber. The inclusion of an inorganic filler is preferable because it reduces the tackiness of the thermoplastic elastomer composition. The content of the filler in the thermoplastic elastomer composition according to one embodiment of the present invention is preferably 150 parts by mass or less, more preferably about 30 to 100 parts by mass, relative to 100 parts by mass of the total of the above (A), (B), and (C).

[0160] The thermoplastic elastomer composition according to one embodiment of the present invention can be produced by kneading each component by a conventionally known method. Kneading is carried out after a mixing step or without a mixing step. The mixing step may be carried out by simultaneously mixing each component of the composition or sequentially, and can be carried out, for example, by mixing using a plastomill, a Henschel mixer, a V-blender, a ribbon blender, a tumbler blender, a kneader, a kneader-ruder, or the like. The kneading can be carried out by adopting a method in which the components are melt-kneaded using a single-screw extruder, a twin-screw extruder, a plastomill, a kneader, a kneader-ruder, a Banbury mixer, or the like, and then granulated, molded, or pulverized. The kneading may be carried out by simultaneously or sequentially adding each component of the composition to a kneading section, or the mixture that has been subjected to the above-mentioned mixing step may be added all at once.

[0161] If desired, a crosslinking agent such as an organic peroxide, a crosslinking assistant, etc. may be added, or these necessary components may be mixed at the same time and melt-kneaded to partially crosslink the material without impairing its thermoplasticity. A crosslinking agent such as an organic peroxide, a crosslinking assistant, etc. may be added to form a crosslinked material. By partially crosslinking or forming a crosslinked material, rubber elasticity at high temperatures is improved, which is preferable. Suitable examples of the crosslinking agent include organic peroxides, and specific examples thereof include 2,5-dimethyl-2,5-di(t-butylperoxy)-hexane; 2,5-dimethyl-2,5-di(benzoylperoxy)-hexane; t-butylperoxybenzoate; dicumyl peroxide; t-butylcumyl peroxide; diisopropylbenzohydroperoxide; 1,3-bis-(t-butylperoxyisopropyl)-benzene; benzoyl peroxide; 1,1-di(t-butylperoxy)-3,3,5-trimethylcyclohexane, and the like. Useful crosslinking assistants include, for example, divinylbenzene, trimethylolpropane triacrylate, ethylene dimethacrylate, diallyl phthalate, quinone dioxime, phenylene bismaleimide, polyethylene glycol dimethacrylate, and unsaturated silane compounds. These organic peroxides and crosslinking aids can be used in an amount of 0.1 to 5 parts by mass when the thermoplastic elastomer composition is taken as 100 parts by mass, to adjust the degree of crosslinking. These organic peroxides and crosslinking aids can be used in combination of two or more kinds as required. When an unsaturated silane compound is used as the crosslinking aid, the crosslinking can be promoted by contacting the compound with moisture in the presence of a silanol condensation catalyst.

[0162] The thermoplastic elastomer composition according to one embodiment of the present invention can be used for various applications without limitation. Since the composition has excellent rubber elasticity, the composition can be suitably used for applications such as sealing materials, packing materials, plugs, automotive interior materials, vibration-damping materials, soundproofing materials, dampers, and daily necessities.

[0163] [Sealing materials, automotive interior materials, vibration damping materials] The thermoplastic elastomer composition according to one aspect of the present invention described above can be appropriately molded by a conventionally known method and used as a sealing material, an automobile interior material, a vibration damping material, etc. Examples of the molding method include injection molding, various extrusion moldings, compression molding, calendar molding, vacuum molding, etc. Also, during molding, a known chemical foaming agent or a known physical foaming agent such as carbon dioxide gas, nitrogen gas, water, etc. can be used to foam the composition by a known method to form a foam.

[0164] The thermoplastic elastomer composition can be used in combination with a support made of a hard resin or metal. The hard resin is not particularly limited, and engineering plastics such as polyolefins such as polypropylene, polyethylene, and polybutene, polyamide, polycarbonate, polyethylene terephthalate, polyacetal, polyphenylene ether, polybutylene terephthalate, polysulfone, and polyimide can be used. The metal is not particularly limited, and can be appropriately selected from, for example, cold-rolled steel plate, zinc-plated steel plate, aluminum / zinc alloy-plated steel plate, stainless steel plate, aluminum plate, aluminum alloy plate, magnesium plate, and magnesium alloy plate. Magnesium injection molding can also be used. Among the above supports, polypropylene is particularly preferred because it has excellent adhesion to the thermoplastic elastomer composition.

[0165] As a method for combining the thermoplastic elastomer composition with a support, a conventionally known molding method such as injection molding or extrusion molding can be adopted. Although not particularly limited, for example, a two-color injection molding method can be adopted in which a hard resin to be a support is melt-injected into a mold, and then a thermoplastic elastomer composition according to one embodiment of the present invention is melt-injected on it, and the thermoplastic elastomer composition is laminated and integrated on the surface of the hard resin molded product. Alternatively, an insert molding method can be adopted in which a hard resin is melt-injected into a mold, and then the molded product is inserted into another mold, and the thermoplastic elastomer composition according to one embodiment of the present invention is melt-injected on the surface of the molded product, and the thermoplastic elastomer composition is laminated and integrated on the surface of the plastic molded product. Alternatively, a metal support can be inserted into a mold, and the thermoplastic elastomer composition according to one embodiment of the present invention is melt-injected on the surface of the molded product, and the thermoplastic elastomer composition can be laminated on the surface of the plastic molded product. Alternatively, a two-color extrusion molding method can be used in which a support and the thermoplastic elastomer composition according to one embodiment of the present invention are simultaneously extruded in a multi-layered form using a molding machine having multiple extruders. Alternatively, a molded article obtained from the thermoplastic elastomer composition can be fixed to the surface of a support using various adhesives. The molded article may be processed by a method such as punching before being fixed to the surface of the support. EXAMPLES

[0166] Hereinafter, one embodiment of the present invention will be described in more detail with reference to examples, but the present invention is not limited to these examples. The raw material components used in the examples and comparative examples are as follows.

[0167] [X / Y block copolymer (A)] In the following Examples and Comparative Examples, the following commercially available X / Y block copolymers were used as the X / Y block copolymer (A). The Mw of each X / Y block copolymer was measured in the same manner as the Mw of the ethylene-α-olefin copolymer described below.

[0168] A-1: Polystyrene-poly(ethylene / butene)-polystyrene block copolymer (SEBS), Kuraray Co., Ltd. Septon 8004 (styrene content: 31% by mass, MFR (230°C, 2.16 kg): <0.1 g / 10 min, Mw: 110,000) A-2: Polystyrene-poly(ethylene / ethylene / propylene)-polystyrene block copolymer (SEEPS), Kuraray Co., Ltd. Septon 4044 (styrene content: 32% by mass, MFR (230°C, 2.16 kg): not flowing, cannot be measured, Mw: 160,000)

[0169] [Ethylene-α-olefin copolymer (B)] The methods for measuring various physical properties of ethylene-α-olefin copolymer (B) are as follows.

[0170] <Kinematic viscosity at 100℃, Kinematic viscosity at 40℃> The kinetic viscosity at 100° C. (100° C. kinetic viscosity) and the kinetic viscosity at 40° C. (40° C. kinetic viscosity) were measured and calculated according to the method described in JIS K 2283.

[0171] <Weight average molecular weight (Mw), molecular weight distribution (Mw / Mn)> The weight average molecular weight (Mw) and molecular weight distribution (Mw / Mn) of the ethylene-α-olefin copolymer (B) were determined by the following high-speed GPC measurement equipment. High-speed GPC measurement device: Tosoh HLC8320GPC Mobile phase: THF (Wako Pure Chemical Industries, Ltd., stabilizer-free, liquid chromatography grade) Column: Two Tosoh TSKgel Super MultiporeHZ-M columns connected in series Sample concentration: 5mg / mL Mobile phase flow rate: 0.35mL / min Measurement temperature: 40℃ Standard sample for calibration curve: Tosoh PStQuick MP-M

[0172] <Ethylene content (mol%)> The ethylene content of the ethylene-α-olefin copolymer (B) was measured using a nuclear magnetic resonance spectrometer (ECP500, manufactured by JEOL Ltd.) with a mixed solvent of orthodichlorobenzene / heavy benzene (80 / 20% by volume) as the solvent, a sample concentration of 55 mg / 0.6 mL, a measurement temperature of 120°C, and observation nuclei of 13 The measurements were performed using C (125 MHz), a single pulse proton decoupling sequence, a pulse width of 4.7 μ / s (45° pulse), a repetition time of 5.5 seconds, an accumulation count of 10,000 or more, and a chemical shift reference value of 27.50 ppm.

[0173] The ethylene content of the ethylene-α-olefin copolymer (B) was measured as described above. 13 The values ​​were calculated from C-NMR spectra based on the reports of "Polymer Analysis Handbook" (published by Asakura Publishing, pp. 163-170), GJ Ray (Macromolecules, 10, 773 (1977)), JC Randal (Macromolecules, 15, 353 (1982)), and K. Kimura (Polymer, 25, 4418 (1984)).

[0174] [Production of ethylene-α-olefin copolymer (B)] The method for producing the ethylene / α-olefin copolymer (B) used in the examples and comparative examples is described below.

[0175] [Production Example 1] Production of ethylene-propylene copolymer (B-1) In a 2-liter continuous polymerization reactor equipped with an agitator and thoroughly purifying the atmosphere with nitrogen, 1 liter of dehydrated and purified hexane was placed, and ethylaluminum sesquichloride (Al(C2H5) 1.5 ·Cl 1.5 A hexane solution of VO(OC2H5)Cl2 adjusted to 16 mmol / L was continuously fed at 500 mL / h for 1 hour, and then a hexane solution of VO(OC2H5)Cl2 adjusted to 16 mmol / L as a catalyst was continuously fed at 500 mL / h, and hexane was continuously fed at 500 mL / h. Meanwhile, the polymerization liquid was continuously withdrawn from the top of the reactor so that the polymerization liquid in the reactor was always 1 L.

[0176] Next, ethylene gas was supplied at a rate of 27 L / h, propylene gas at a rate of 26 L / h, and hydrogen gas at a rate of 100 L / h using a bubbling tube. The copolymerization reaction was carried out at 35°C by circulating a coolant through a jacket attached to the outside of the reactor. This resulted in a polymerization solution containing an ethylene-propylene copolymer.

[0177] The obtained polymerization solution was washed three times with 500 mL of 0.2 mol / L hydrochloric acid per 1 L of the polymerization solution, and then three times with 500 mL of distilled water per 1 L of the polymerization solution. After drying over magnesium sulfate, the solvent was distilled off under reduced pressure. The obtained viscous liquid was dried under reduced pressure at 130°C for 24 hours to obtain an ethylene-propylene copolymer (B-1). The ethylene content of this ethylene-propylene copolymer (B-1) was 53.0 mol%, Mw was 2,700, Mw / Mn was 1.5, and 100°C kinetic viscosity was 40 mm 2 / s, 40℃ kinematic viscosity is 400mm 2 / s.

[0178] [Production Example 2] Production of ethylene-propylene copolymer (B-2) 760 mL of heptane and 120 g of propylene were charged into a 2 L stainless steel autoclave that had been thoroughly purged with nitrogen, and the temperature inside the system was raised to 150°C. Then, 0.85 MPa of hydrogen and 0.19 MPa of ethylene were fed to adjust the total pressure to 3 MPa-G. Next, 0.4 mmol of triisobutylaluminum, [methylphenylmethylene (η 5 -cyclopentadienyl)(η 50.0002mmol of N,N-dimethylanilinium tetrakis(pentafluorophenyl)borate was added with nitrogen and polymerization was started by changing the stirring speed to 400rpm. Then, the total pressure was kept at 3MPa-G by continuously supplying only ethylene, and polymerization was carried out at 150℃ for 5 minutes. After the polymerization was stopped by adding a small amount of ethanol to the system, unreacted ethylene, propylene, and hydrogen were purged. The obtained polymerization solution was washed three times with 1000mL of 0.2mol / L hydrochloric acid and then three times with 1000mL of distilled water, dried over magnesium sulfate, and the solvent was removed under reduced pressure to obtain a crude ethylene-propylene copolymer.

[0179] In a 1L stainless steel autoclave, 100mL of a hexane solution of 0.5% by mass Pd / alumina catalyst and 500mL of a 30% by mass hexane solution of the obtained crude ethylene-propylene copolymer were added, the autoclave was sealed, and then nitrogen replacement was performed. Next, the temperature was raised to 140°C while stirring, and the inside of the system was replaced with hydrogen, and the pressure was raised to 1.5 MPa with hydrogen to perform a hydrogenation reaction for 15 minutes. The reaction solution was filtered to remove the hydrogenation catalyst, and the solvent was distilled off under reduced pressure. The mixture was dried at 80°C under reduced pressure for 24 hours to obtain an ethylene-propylene copolymer (B-2). The ethylene content of this ethylene-propylene copolymer (B-2) was 48.5mol%, Mw was 5,200, Mw / Mn was 1.7, and the 100°C kinetic viscosity was 152mm 2 / s, 40℃ kinematic viscosity is 2,210mm 2 / s.

[0180] [Production Example 3] Production of ethylene-propylene copolymer (B-3) 760 mL of heptane and 120 g of propylene were charged into a 2 L stainless steel autoclave that had been thoroughly purged with nitrogen, and the temperature inside the system was raised to 150°C. Then, 0.85 MPa of hydrogen and 0.19 MPa of ethylene were fed to adjust the total pressure to 3 MPa-G. Next, 0.4 mmol of triisobutylaluminum, [diphenylmethylene (η 5 -3-n-butylcyclopentadienyl)(η5 0.0002mmol of N,N-dimethylanilinium tetrakis(pentafluorophenyl)borate was added with nitrogen and polymerization was started by changing the stirring speed to 400rpm. Then, polymerization was carried out at 150℃ for 5 minutes while maintaining the total pressure at 3MPa-G by continuously supplying only ethylene. After stopping the polymerization by adding a small amount of ethanol to the system, unreacted ethylene, propylene, and hydrogen were purged. The obtained polymerization solution was washed three times with 1000mL of 0.2mol / L hydrochloric acid and then three times with 1000mL of distilled water, dried over magnesium sulfate, and the solvent was removed under reduced pressure. The obtained polymer was dried at 80℃ under reduced pressure for 24 hours to obtain ethylene-propylene copolymer (B-3). The ethylene content of this ethylene-propylene copolymer (B-3) is 49.5 mol%, Mw is 5,100, Mw / Mn is 1.7, and kinematic viscosity at 100°C is 150mm 2 / s, 40℃ kinematic viscosity is 2,200mm 2 / s.

[0181] [Polyolefin resin (C)] In the following Examples and Comparative Examples, the following commercially available polyolefin resins were used as the polyolefin resin (C). C-1: Homopolypropylene, Prime Polypro J105G manufactured by Prime Polymer Co., Ltd. (MFR (230°C, 2.16 kg): 9 g / 10 min)

[0182] [Other oils (D)] In the comparative examples below, the following commercially available oils were used. D-1: Paraffin-based mineral oil, Diana Process Oil PW-90 manufactured by Idemitsu Kosan Co., Ltd. D-2: Paraffin-based mineral oil, Diana Process Oil PW-380 manufactured by Idemitsu Kosan Co., Ltd. D-3: Liquid paraffin, MORESCO White P-350P manufactured by MORESCO Corporation

[0183] [Examples 1 to 12, Comparative Examples 1 to 7] X / Y block copolymers (A-1), (A-2), ethylene-α-olefin copolymers (B-1)-(B-3), polyolefin resin (C-1), and other oils (D-1)-(D-3) were mixed in a twin-screw extruder in the ratios shown in Table 1, and the extruded strands were cut to prepare pellets. The pellets were dried at 80°C for 12 hours, and then pressed into sheets measuring 2 mm thick and 200 mm square using a thermal compressor. Test pieces for physical property tests were prepared from these sheets.

[0184] Subsequently, the physical properties of the composition were evaluated by the following methods. (1) Hardness According to JIS K 6253-3:2012, three press sheets were stacked and the type A durometer hardness was measured. (2)MFR According to JIS K 7210-1:2014, the measurement was carried out using the above pellets under conditions of 230°C and 2.16 kg. (3) Compression set (CS) In accordance with JIS K 6262:2013, six test pieces were punched out from the above press sheet to create disks measuring 29 mm in diameter and 2 mm in thickness, which were then stacked and compressed by 25% before being placed in a thermostatic chamber at 50°C or 70°C. After 24 hours, the test pieces were removed from the thermostatic chamber and the compression set was measured using JIS Method A. (4) Permanent set (PS) In accordance with JIS K 6273:2018, JIS dumbbell-shaped No. 3 test pieces were punched out from the above press sheet, and then elongated by 20% or 100% and placed in a thermostatic chamber at 50°C or 70°C. After 24 hours, the test pieces were removed from the thermostatic chamber and the constant elongation permanent tensile set was measured using JIS method A. The measurement results are shown in Tables 1 to 5.

[0185] [Table 1]

[0186] [Table 2] As shown in Tables 1 and 2, when evaluation was performed with a test piece hardness of about 59 to 65, Examples 1 to 7, which used ethylene-α-olefin copolymer (B), had lower physical property values ​​indicating resistance to sagging, such as compression set and permanent elongation, and were therefore superior in resistance to sagging, compared to Comparative Examples 1 to 3, which used (D-1) to (D-3) instead of copolymer (B).

[0187] [Table 3] As shown in Table 3, when evaluation was performed with a test piece hardness of about 39 to 50, Examples 8 and 9, which used ethylene-α-olefin copolymer (B), showed lower physical property values ​​indicating resistance to sagging, such as compression set and permanent elongation, and thus showed superior resistance to sagging, compared to Comparative Examples 4 and 5, which used (D-2) instead of copolymer (B).

[0188] [Table 4] As shown in Table 4, when the test pieces were evaluated at a hardness of about 75 to 77, Example 10, which used ethylene-α-olefin copolymer (B), had lower physical property values ​​indicating resistance to sagging, such as compression set and permanent elongation, and thus had superior resistance to sagging, compared to Comparative Example 6, which used (D-2) instead of copolymer (B).

[0189] [Table 5] As shown in Table 5, when (A-2) was used instead of (A-1) as the X / Y block copolymer (A) and evaluation was performed with a composition having a test piece hardness of about 62 to 65, Examples 11 and 12, which used the ethylene-α-olefin copolymer (B), showed lower physical property values ​​indicating resistance to sag, such as compression set and permanent elongation, and thus showed excellent resistance to sag, compared to Comparative Example 7, which used (D-1) instead of the copolymer (B).

Claims

1. 100 parts by mass of a block copolymer or a hydrogenated product thereof (A) containing a polymer block (X) mainly composed of a vinyl aromatic compound and a polymer block (Y) mainly composed of a conjugated diene compound; 1 to 400 parts by mass of an ethylene / α-olefin copolymer (B) satisfying the following requirements (b-1) to (b-3); 10 to 200 parts by mass of a polyolefin resin (C) satisfying the following requirement (c-1); (However, this does not include a thermoplastic elastomer composition containing an ethylene / α-olefin copolymer having a kinetic viscosity at 100°C of 300 to 5000 mm2 / s, a kinetic viscosity at 40°C of 4000 to 100,000 mm2 / s and an ethylene structural unit content of 30 to 80 mol%, and a thermoplastic elastomer composition having an MFR of 5 g / 10 min measured at 230°C under a load of 2.16 kg in accordance with ASTM D1238.) (b-1) 100° C. kinematic viscosity of 5 to 5,000 mm 2 / s, and the 40°C kinematic viscosity is 50 to 100,000 mm 2 / s. (b-2) The weight average molecular weight (Mw) determined by gel permeation chromatography (GPC) is 1,000 to 30,000. (b-3) The content of ethylene structural units is 15 to 85 mol %. (c-1) MFR (230°C, 2.16 kg) is 0.1 to 500 g / 10 min.

2. the block copolymer or hydrogenated product thereof (A) is a hydrogenated product of a block copolymer containing a polymer block (X) mainly made of a vinyl aromatic compound and a polymer block (Y) mainly made of a conjugated diene compound, The thermoplastic elastomer composition according to claim 1, wherein a content ratio of the ethylene / α-olefin copolymer (B) is 30 to 300 parts by mass, and a content ratio of the polyolefin resin (C) is 10 to 150 parts by mass, relative to 100 parts by mass of the hydrogenated block copolymer.

3. In the above requirement (b-1), the 100° C. kinematic viscosity is 30 to 300 mm 2 / s, and the 40°C kinematic viscosity is 300 to 4,000 mm 2 / s, and In the above requirement (b-2), the weight average molecular weight (Mw) determined by gel permeation chromatography (GPC) is 2,000 to 7,000; and The thermoplastic elastomer composition according to claim 1 or 2, wherein, in the requirement (b-3), the content of ethylene structural units is 40 to 60 mol %.

4. The thermoplastic elastomer composition according to any one of claims 1 to 3, wherein the polymer block (X) is a polymer block mainly composed of styrene, the polymer block (Y) is a copolymer block mainly composed of butadiene and isoprene, and the block copolymer or hydrogenated product thereof (A) is a hydrogenated product of the block copolymer.

5. A sealing material comprising the thermoplastic elastomer composition according to any one of claims 1 to 4.

6. An automobile interior material comprising the thermoplastic elastomer composition according to any one of claims 1 to 4.

7. A vibration damping material comprising the thermoplastic elastomer composition according to any one of claims 1 to 4.

8. 100 parts by mass of a block copolymer or a hydrogenated product thereof (A) containing a polymer block (X) mainly composed of a vinyl aromatic compound and a polymer block (Y) mainly composed of a conjugated diene compound; 1 to 400 parts by mass of an ethylene / α-olefin copolymer (B) produced by the following method (α) and satisfying the following requirements (b-1) to (b-3); 10 to 200 parts by mass of a polyolefin resin (C) satisfying the following requirement (c-1); a thermoplastic elastomer composition containing an ethylene-α-olefin copolymer having a kinetic viscosity at 100°C of 300 to 5000 mm2 / s, a kinetic viscosity at 40°C of 4000 to 100,000 mm2 / s, and an ethylene structural unit content of 30 to 80 mol%, and a thermoplastic elastomer composition having an MFR of 5 g / 10 min measured at 230°C under a load of 2.16 kg in accordance with ASTM D1238, comprising: (b-1) 100° C. kinematic viscosity of 5 to 5,000 mm 2 / s, and the 40°C kinematic viscosity is 50 to 100,000 mm 2 / s. (b-2) The weight average molecular weight (Mw) determined by gel permeation chromatography (GPC) is 1,000 to 30,000. (b-3) The content of ethylene structural units is 15 to 85 mol %. (c-1) MFR (230°C, 2.16 kg) is 0.1 to 500 g / 10 min. Method (α): A bridged metallocene compound (P-1) represented by the following formula [1], and At least one compound (Q) selected from the group consisting of an organometallic compound (Q-1), an organoaluminum oxy compound (Q-2) and a compound (Q-3) which reacts with the bridged metallocene compound (P-1) to form an ion pair.

2. A process comprising the step of solution polymerizing ethylene and an α-olefin in the presence of a catalyst system comprising: 【Chemistry 1】 [In formula [1], R 1 , R 2 , R 3 , R 4 , R 5 , R 8 , R 9 and R 12 each independently represents a hydrogen atom, a hydrocarbon group, or a silicon-containing hydrocarbon group, and adjacent groups may be linked to each other to form a ring structure; R 6 and R 11 are the same group and each is a hydrogen atom, a hydrocarbon group, or a silicon-containing hydrocarbon group, R 7 and R 10 are the same group and each is a hydrogen atom, a hydrocarbon group, or a silicon-containing hydrocarbon group, R 6 and R 7 may be bonded to a hydrocarbon having 2 to 3 carbon atoms to form a ring structure, R 10 and R 11 may be bonded to a hydrocarbon having 2 to 3 carbon atoms to form a ring structure, R 6 , R 7 , R 10 and R 11 is not a hydrogen atom at the same time; Y is a carbon atom or a silicon atom; R 13 and R 14 each independently represents a hydrogen atom, a hydrocarbon group, or a silicon-containing hydrocarbon group, and may be linked together to form a ring structure; M is Ti, Zr or Hf; Q is independently a halogen atom, a hydrocarbon group, an anionic ligand, or a neutral ligand capable of coordinating with a lone pair of electrons; j is an integer from 1 to 4.

9. In the formula [1], R 13 and R 14 The method according to claim 8 , wherein either or both of the above is an aryl group.

10. In the formula [1], R 13 and R 14 are both aryl groups, and R 2 and R 3 The method according to claim 8 or 9, wherein either one of the above is a saturated hydrocarbon group having 4 carbon atoms.

11. The production method according to any one of claims 8 to 10, wherein the polymer block (X) is a polymer block mainly composed of styrene, the polymer block (Y) is a copolymer block mainly composed of butadiene and isoprene, and the block copolymer or hydrogenated product thereof (A) is a hydrogenated product of the block copolymer.

Citation Information

Patent Citations

  • Production of rubbery olefin copolymer

    JP1987000512A

  • Elastomer composition for cap liner and cap liner made therefrom

    JP1999106565A

  • Thermoplastic elastomer composition

    JP2000273249A

  • Synthetic lubricating oil and lubricating oil composition

    JP2006176760A

  • Polymer composition and method for producing the same, and use of the same

    JP2015160886A